Marine algae as a source of bioactive nanofibers: Innovations in tissue repair and skin regeneration - Lucas Alexandre da Silva; Saeid Ali Bozorgzadeh; Patrícia Danielle Oliveira de Almeida; Morteza Golbashirzadeh (Tissue and Cell, 2027)

Wildfire smoke, PM2.5 exposure and respiratory morbidity in a densely populated urban setting: Spatial mapping and time-series evidence - Egle Gabriele Castanha de Souza; Bruno Iartelli Silva; Alexandre Matos Muniz Matias; Luis Felipe de Almeida Duarte (Science of The Total Environment, 2026)

Radiographic and morphological prevalence of dorsopalmar hoof distortions in Brazilian high-performance racehorses - Mayara Gomes Correa; Jéssica Fontana de Magalhães; Julia Renault Baeta Guedes; Armando de Mattos Carvalho; Luiz Alberto do Lago; Alexandre Augusto de Oliveira Gobesso; Beatriz Nogueira Ferreira; Fernanda Pereira de Almeida Manzano de Campos; Reinaldo de Campos; Rafael Resende Faleiros (Journal of Equine Veterinary Science, 2026)

Collaborative monitoring networks refine jaguar habitat suitability and reveal conservation gaps in the Brazilian Cerrado - Lucas Gonçalves da Silva; Marco Aurélio Mendes Elias; Juliana Silveira dos Santos; Anah Tereza de Almeida Jácomo; Douglas Santos; Ennio Painkow Neto; Fabio Hudson Souza Soares; Gabriel Caputo de Carvalho; Giselle Bastos Alves; Gonzalo Barquero; Igor Fagundes Perfeito; Marina Motta de Carvalho; et al. (Biological Conservation, 2026)

First report of free-ranging maned wolf (Chrysocyon brachyurus) coinfected with Dioctophyma renale and Pearsonema sp. in Brazil - Alexandre Carvalho Costa; Elisabeth Neves Mureb; Naiara Vidal Stocco; Ágatha Ferreira Xavier de Oliveira; Bruna Emely Pereira Barbosa; Cristiano Chaves Pessoa da Veiga; Andresa Guimarães; Juliana Macedo Raimundo; Huarrisson Azevedo Santos; Daniel de Almeida Balthazar; Cristiane Divan Baldani (Veterinary Research Communications, 2026)
The manned wolf ( Chrysocyon brachyurus ) has a highly diversified diet, that includes fish and amphibians, which may harbor infective forms of parasites, such as Dioctophyma renale and Pearsonema (syn. Capillaria ) spp. Both parasites affect the urinary tract of their hosts, with D. renale being capable of infecting a wide range of mammalian species, whereas Pearsonema spp. exclusively parasitizes wild and domestic canids and felids, releasing their eggs in the urine of the host. This study reports the first coinfection by D. renale and Pearsonema sp. in the urine of a free-ranging maned wolf as well as associated laboratory findings. A male adult maned wolf, injured in a train accident in an urban area, was referred to the Centro de Triagem de Animais Silvestres (CETAS) – Rio de Janeiro, Brazil, where hemogram, biochemistry, ultrasonography, and urinalysis were performed. Ultrasonography examination revealed findings consistent with parasitism by D. renale in the right kidney and right perirenal region. Urinary sediment examination showed D. renale (5/field) and Pearsonema sp. eggs (1/field). Egg morphometry was performed, yielding mean length and width values of 62.2 μm and 41.2 μm for D. renale and 58.0 μm and 26.1 μm for Pearsonema sp., respectively. Through sediment examination and morphometry, it was possible to confirm Pearsonema sp. and D. renale infection, the latter also confirmed by ultrasonography, highlighting the importance of urinalysis in wild animals and demonstrating the need for continuous investigation into Pearsonema spp. which are poorly studied in wild canids.

Sublethal toxicity of selenium nanoparticles in zebrafish early life stages: biochemical and behavioral responses - Pearl Ofoegbu; Rita Duarte; Soraia Almeida; Alexandre Marques; David Daniel; Luís Barros; Ricardo J. B. Pinto; Victor Galhano; Bruno Nunes (Environmental Science and Pollution Research, 2026)

Seed desiccation tolerance and conservation of sapucaia, an emerging functional Brazil nut tree from the Atlantic and Amazon forest biomes - Caroline Palacio de Araujo; Ingridh Medeiros Simões; Joana Silva Costa; Taísa de Fátima Rodrigues de Almeida; Débora Pellanda Fagundes; Eduardo Santos Cade; Emanuel Bizareli de Moraes; Jéssica Batista Ribeiro e Oliveira; Edilson Romais Schmildt; José Eduardo Macedo Pezzopane; José Carlos Lopes; Heloisa Oliveira dos Santos; et al. (Journal of Stored Products Research, 2026)

Land-use impacts on a soil ecosystem services index in the Brazilian Atlantic Forest biome - Maria Cecília Vieira Totti; Sérgio Henrique Godinho Silva; Bruno Montoani Silva; Ricardo de Oliveira Bordonal; Fernanda Almeida Bócoli; Vanêssa Lopes de Faria; Adriana Marcela Silva-Olaya; Andrés Olaya Montes; Alexandre Uezu; Laury Cullen Junior; Vinícius Ferreira Fernandes; Junior Cesar Avanzi (Geoderma Regional, 2026)

Dietary intervention with purple passion fruit peel in asthma: insights into Th2-mediated responses in an ovalbumin-induced murine model - Alexandre M.A. Fonseca; Roberto de Paula do Nascimento; Levi Bellinazzi; Cátia Vieira; Adelaide Almeida; Renata Galhardo Borguini; Cláudia C. Loureiro; Mário R. Maróstica Junior; Armando J.D. Silvestre; Sílvia M. Rocha (Food Research International, 2026)

Productive, metabolic and economic responses of Nellore young bulls fed diets with different non-protein nitrogen source combinations - Luiz Antonio Rodrigues; Priscilla Dutra Teixeira Borges; Camila Celeste Brandão Ferreira Ítavo; Gelson dos Santos Difante; Alexandre Menezes Dias; Vanessa Zirondi Longhini; Manoel Gustavo Paranhos da Silva; Lívia do Nascimento Gomes; Adrianni Dias Borges; Hevelyn de Almeida Cunha; Luís Carlos Vinhas Ítavo (Tropical Animal Health and Production, 2026)
Nutrition is a key determinant of performance, carcass traits, and production efficiency in beef cattle. In this context, feed additives have emerged as a promising strategy to enhance nutrient utilization and reduce production costs. We aimed to evaluate the effects of replacing urea with a product extruded urea enriched with essential oils (NFeed ® ) on nutrient intake, performance, blood parameters, and feed cost in feedlot-finished Nellore young bulls. Twenty-four non-castrated animals with an average initial body weight of 394.6 ± 53 kg were randomly assigned in a completely randomized design, following the treatments considering different combinations of NPN source in diet: 0% NFeed (100% of non-protein nitrogen from urea), 50% NFeed (50% of non-protein nitrogen from urea and 50% of non-protein nitrogen from NFeed), 75% NFeed (25% of non-protein nitrogen from urea and 75% of non-protein nitrogen from NFeed) and 100% NFeed (100% of non-protein nitrogen from NFeed). Final body weight, total weight gain, and average daily gain had a linear response, with the highest values in the 100% NFeed treatment. Feed efficiency and feed conversion exhibited linear effects, with the 100% NFeed diet resulting in the greatest feed efficiency and the lowest feed conversion. A quadratic effect was observed for plasma urea, and gamma-glutamyl transferase levels. The replacement of conventional urea with extruded urea enriched with essential oils (NFeed) represents a viable nutritional strategy for finishing beef cattle in feedlot systems. Increasing levels of NFeed linearly improved animal performance while maintaining similar feed intake, increasing feed efficiency reducing feed conversion, and the cost per kilogram of body weight gain. Thus, we recommend a partial replacement of urea by NFeed as a non-protein source in beef cattle feedlot.

Nonlinear Modeling of Sugarcane Yield Based on Edaphic Attributes and Soil Classes - Tays Silva Batista; Luiz Alexandre Peternelli; Ivan Carlos Carreiro Almeida; André Mundstock Xavier de Carvalho (Sugar Tech, 2026)
Edaphic attributes strongly influence sugarcane yield, yet production environments are commonly classified based on average productivity, which may not fully capture environmental variability. This study evaluated how physicochemical soil attributes and soil classes influence sugarcane productivity and whether integrating nonlinear modeling and multivariate analyses improves the characterization of production environments. Edaphic data obtained from SoilGrids and mean Tons of Stalks per Hectare (TSH) per genotype, environment, and harvest cycle collected between 2018 and 2021 were used. Generalized additive models (GAMs) were fitted to assess the effects of soil classes and continuous soil attributes on productivity, while principal component analysis (PCA) and hierarchical clustering were used to identify edaphic gradients and group environments according to soil similarity. The GAM explained 67% of the variance in TSH and revealed significant nonlinear effects of bulk density, cation exchange capacity (CEC), silt, nitrogen, and organic carbon across soil depths. Soil class also significantly affected productivity, with LATOSSOLO VERMELHO Distrófico (LVd) associated with the highest TSH values. PCA identified two major edaphic gradients related to texture/fertility and surface fertility, and clustering grouped environments into four distinct edaphic profiles. Comparison with the traditional productivity-based classification showed that environments with similar TSH can exhibit markedly different soil characteristics, indicating that average yield alone is insufficient to describe environmental variability. Integrating nonlinear modeling and multivariate soil characterization provides a more informative framework for environmental stratification, supporting genotype recommendation and agronomic management in sugarcane production systems.

First Report of Mansonella sp. Microfilariae in Sapajus nigritus: Insights into the Host-Parasite Relationship - Juliana de Moura Medeiros; Diogo Pignatara Coimbra; Alexandre Carvalho Costa; Ana Elisa Barros Medeiros; Beatriz Pereira Coelho; Gustavo Azevedo Quintanilha; Claudia Bezerra da Silva; Jonathan David Ribas Chagas; Cristiane Divan Baldani; Daniel de Almeida Balthazar; Bruna de Azevedo Baeta; Denise Monnerat Nogueira (International Journal of Primatology, 2026)
Primates can share parasites with humans, and understanding host-parasite interactions is essential for evaluating the condition of wild primates, ecological dynamics, and One Health interface, which integrates humans, animal, and environmental health in shared environments. One example is filarial nematodes of the genus Mansonella , for which a lack of in-depth studies of symptoms or blood alterations limits our understanding of their impact on host health and parasite-host dynamics in wild populations. We investigated microfilariae in Sapajus nigritus on Marambaia Island in Rio de Janeiro, Brazil. We also evaluated the host-parasite relationship by assessing the association between microfilarial load with physical and hematological parameters of the hosts. We captured 27 S. nigritus and screened them for microfilariae using blood samples via microscopy—based on morphological and morphometric characteristics—and polymerase chain reaction (PCR), followed by ITS1 sequencing for molecular species identification. We also assessed physical and hematological parameters. We detected microfilariae in 25 individuals (93%) by PCR and in 22 (81%) by microscopy with high mean intensity, mean abundance, and parasite load. We classified the infected S. nigritus as healthy based on both physical and hematological parameters. A multivariate linear model revealed a significant positive association between Mansonella sp. load and red blood cell parameters, while associations with white blood cell parameters were negative and nonsignificant. These results suggest that S. nigritus coexists with Mansonella sp. microfilariae without apparent clinical signs of disease, potentially indicating immunological tolerance. Our findings highlight the importance of understanding host-parasite interactions in wild primates, particularly in environments where human-primate interfaces may occur, suggesting a potential risk of cross-species parasite transmission.

Retraction notice to “Spatial and temporal distribution of urban heat islands” [Sci. Total Environ. 605–606 (2017) 946–956] - Alexandre Rosa dos Santos; Felício Santos de Oliveira; Aderbal Gomes da Silva; José Marinaldo Gleriani; Wantuelfer Gonçalves; Giselle Lemos Moreira; Felipe Gimenes Silva; Elvis Ricardo Figueira Branco; Marks Melo Moura; Rosane Gomes da Silva; Ronie Silva Juvanhol; Kaíse Barbosa de Souza; et al. (Science of The Total Environment, 2026)

Corrigendum to “Conservation gaps and the essential role of Indigenous Lands in protecting small non-volant mammals in Brazilian Amazonian” [ J. Nat. Conserv. 91 (2026) 127242] - Simone Almeida Pena; Cláudia Regina da Silva; Rafaela Jemely Rodrigues Alexandre; Thiago Bernardi Vieira (Journal for Nature Conservation, 2026)

A new neotropical Bruggmanniella Tavares, 1909 (Diptera: Cecidomyiidae) inducing galls on commercial avocado - Carolina de Almeida Garcia; Maria Virginia Urso; Grazielle Furtado Moreira; Alexandre José Ferreira Diniz (Applied Entomology and Zoology, 2026)
Brazil is among the world’s leading avocado producers, with cultivation increasingly threatened by gall-inducing midges that damage blossoms and impair fruit development. During surveys in commercial Hass avocado orchards in Minas Gerais, Brazil, a previously unknown species of Bruggmanniella Tavares, 1909 (Diptera: Cecidomyiidae) was discovered infesting young fruits. Here, we describe Bruggmanniella abacate sp. nov. Garcia and Urso, based on larvae, pupae, males, and females reared from malformed fruit galls. Larvae develop within the ovarian tissue, inducing elongated galls that lead to fruit abortion. This is the first record of a Bruggmanniella species associated with Persea americana Mill. cv. ‘Hass’ in Brazil. Our findings reveal previously undocumented diversity of avocado-infesting gall midges and underscore the need for further studies to evaluate their distribution, biology, and potential economic impact on the expanding Brazilian avocado production.

CO2 removal by applying the adsorption process to biochar from waste materials - Maria Angelica Martins Costa; Geisa Albini; Lucas Freitas de Oliveira; Eliza Almeida de Oliveira; Alexandre Jorge Duarte de Souza; Mariana de Oliveira Bérgamo; Letícia Vicente Moreno; Kelly Johana Dussán (Environmental Science and Pollution Research, 2026)
This study evaluated lignocellulosic residues as low-cost adsorbents for CO 2 capture in a dynamic column system, focusing on spent coffee grounds biochar (SCGB) as an alternative to commercial activated carbon. Commercial activated carbon, SCGB, magnetized SCGB, KOH-activated SCGB, peanut shell pellet charcoal, sugarcane bagasse charcoal containing kaolin, and calcined SCGB samples were tested. SCGB was produced by pyrolysis and modified by chemical activation, magnetite incorporation, or post-pyrolysis calcination. CO 2 adsorption tests were performed in a column under different air and CO₂ inlet flow rates, and CO 2 concentrations were monitored at the inlet and outlet using infrared sensors. The adsorption capacity ranged from 0.43 to 7.17 mmol CO 2 /g, depending on the adsorbent and operating conditions. The best performance was obtained for non-activated SCGB, which reached 7.17 mmol CO 2 /g under intermediate air flow conditions. Although KOH activation improved the textural properties of SCGB, it did not lead to the highest adsorption capacity in the column. These results indicate that CO 2 capture under dynamic conditions is controlled not only by BET surface area and micropore volume, but also by pore accessibility, surface chemistry, bed behavior, and gas residence time. Spent coffee grounds biochar showed competitive CO 2 adsorption performance and may be considered a promising low-cost adsorbent for carbon capture applications. The results support the use of biomass-derived residues in column-based CO 2 mitigation processes, while highlighting the need for further studies on humidity tolerance, regeneration, and scale-up.

Nursery habitat use of juvenile meagre (Argyrosomus regius): findings from acoustic telemetry in the Tagus estuary - João P. Marques; Pedro R. Almeida; Nuno Prista; José Lino Costa; Carlos M. Alexandre; Catarina S. Mateus; Isabel Domingos; Patrick Reis-Santos; Bernardo R. Quintella (Marine Biology, 2026)
We used acoustic telemetry to investigate the nursery habitat use of 33 juvenile meagre Argyrosomus regius (mean size = 581 ± 105.1 mm), recording more than 60,000 detections in the Tagus estuary, located in the North-Eastern Atlantic. All individuals used the nursery area from spring to autumn, and a small number (22.2%) remained in the Tagus estuary during winter. Daily movements averaged 6.2 ± 1.9 km, with maximum daily distances reaching 41.2 ± 17.3 km. Peak movement activity was observed in July-October (average distance = 367.3 ± 240.3 km), and predominantly during the night. Furthermore, larger sized individuals returned to the Tagus estuary in subsequent years, typically using this habitat from May to October for an average of 108.5 ± 43.0 days. Spatial analyses indicated that the lower and middle sections of the Tagus estuary serve as important nursery habitats year-round, whereas the upper estuary functions as a nursery primarily from March through June. Network movement analyses highlighted that specific areas in the middle and lower reaches exhibit higher movement activity. Generalized additive modelling indicated that the occurrence of juvenile meagre in the Tagus estuary was significantly influenced by temporal and environmental variables, including day of the year, salinity, dissolved oxygen, and temperature, measured both in the estuary and in the adjacent coastal area. These findings enhance our understanding of the habitat use in estuarine nursery areas and emphasise the importance of incorporating targeted fisheries management strategies in nursery areas to promote the sustainability of this ecologically and economically important fish.

Climate Predicts Tree Dispersal Strategies Across Brazil's Ecosystems - Fernanda C. Souza; Vinícius Andrade Maia; Renata Françoso; Matheus Coutinho Freitas de Oliveira; Ana Beatriz Ligo; Bruno X. Pinho; Jesús Aguirre‐Gutiérrez; Martin Sullivan; Larissa Rocha‐Santos; Laura de Brito Évora; Leonardo de Sousa Miranda; María Natalia Umaña; et al. (Global Ecology and Biogeography, 2026)
Aim We investigate the distribution of dispersal modes — endozoochory (via animal ingestion), synzoochory (via animal seed accumulation) and anemochory (via wind)—and seed mass of woody plants across Brazilian ecosystems, testing whether their relative abundance in local plant communities could be predicted by climate, edaphic factors and dispersal agents (e.g., the main vectors moving seeds). We expected climate to be the main predictor of dispersal strategy abundance. Location Brazilian ecosystems (Amazon, Atlantic Forest, Cerrado and Caatinga). Time Period 2004–2020. Major Taxa Studied Woody angiosperms, trees and shrubs. Methods We assigned seed mass to 1984 species and dispersal mode to 2203 species within 300 old‐growth and non‐flooded plots. We employed Random Forest regressions to assess the influence of water availability, temperature seasonality, soil fertility, wind and frugivorous primates on the community‐weighted means of seed mass and dispersal modes. We mapped predictions and estimated the area of applicability to identify regions where predictions were reliable. Results Climate was the main factor predicting tree dispersal strategies, followed by dispersal agents or soil properties. Endozoochory was prevalent in wetter regions with high water availability and greater diurnal temperature range. Anemochory was more common in drier regions with low water availability, stronger winds and greater diurnal temperature range, whereas synzoochory was more abundant in areas with low temperature seasonality. Heavier seeds were more prevalent in regions with less seasonal temperatures, smaller diurnal temperature ranges and weaker winds. Main Conclusions Climate is a key predictor of the distribution and prevalence of plants with contrasting dispersal modes and seed masses. We thus expect functional responses to environmental change associated with shifts in the relative abundance of dispersal strategies, with implications for ecosystem services. Our results also highlight the critical role of plot‐based datasets in improving our understanding of how environmental factors influence seed dispersal strategies across tropical ecosystems.

Potential of guava pulps treated by ohmic heating as a delivery vehicle for probiotic bacteria: stability, functional properties, and in vitro digestibility - Newton C. Santos; Raphael L.J. Almeida; Virgínia M. de A. Silva; Thalis L.B. de Lima; Ronildo P. de Sousa Júnior; Victor H. de A. Ribeiro; Yaroslávia F. Paiva; Francislaine S. dos Santos; Deyzi S. Gouveia; Rennan P. de Gusmão; Alexandre J. de M. Queiroz; Josivanda P. Gomes; et al. (International Journal of Food Microbiology, 2026)

Conservation gaps and the essential role of Indigenous Lands in protecting small non-volant mammals in Brazilian Amazonian - Simone Almeida Pena; Cláudia Regina da Silva; Rafaela Jemely Rodrigues Alexandre; Thiago Bernardi Vieira (Journal for Nature Conservation, 2026)

Forest restoration enhances soil health in tropical agricultural landscapes assessed by soil management assessment framework (SMAF) across land uses and soil types - Vanêssa Lopes Faria; Helen Carla Santana Amorim; Maria Cecília Vieira Totti; Fernanda Almeida Bócoli; Junior Cesar Avanzi; Sérgio Henrique Godinho Silva; Alexandre Uezu; Amanda J. Ashworth; Gerson L. Drescher; Lara Mota Corinto; Samara Martins Barbosa; Vinícius Ferreira Fernandes; et al. (Geoderma Regional, 2026)

Analysis of the physical and chemical characteristics of stored and fresh Leucaena leucocephala seeds - Viviane da Silva Sousa Almeida; Amanda Graziela Gonçalves Mendes; Tonicley Alexandre da Silva; Daniele Gomes Cassias Rodrigues; Ariadina Jansen Campos Fontes; José Lima Pereira-Filho; Carmem Duarte Lima Campos; Aleania Polassa Almeida Pereira; João Lucas do Carmo Lima; Kátia Danielle Araújo Lourenço Viana; Valério Monteiro-Neto (Food Research International, 2026)

Dietary biological silage from tambaqui by products affect performance, physiology, and egg quality of young and old laying hens - Cristiane Cunha Guimarães; João Paulo Ferreira Rufino; Alexandre Augusto Barai; Adriene Núzia de Almeida Santos; Maria Fernanda da Silva Gomes; Tiago Cabral Nóbrega; Maiko Willas Soares Ribeiro; Philip Dalbert da Silva Castro; Joana Maia Mendes; Francisco Alberto de Lima Chaves; Joel Lima da Silva Junior; Marco Antonio de Freitas Mendonça; et al. (Tropical Animal Health and Production, 2026)
This study evaluated the effects of increasing inclusion levels of biological silage produced from tambaqui ( Colossoma macropomum ) by-products (BST) in diets of commercial hens at different ages. A completely randomized design in a 2 × 5 factorial arrangement was adopted, comprising two hen ages (23 and 83 weeks) and five BST inclusion levels (0, 1, 2, 3, and 4%), with four replicates of six birds per treatment. Moderate BST inclusion (1–2%) improved egg production, egg mass, and feed efficiency, particularly in younger hens, while maintaining physiological homeostasis. In contrast, higher inclusion levels (≥ 3%) reduced feed intake and performance and negatively affected erythropoietic indicators, with more pronounced effects in older hens, highlighting age-dependent metabolic responses. Egg physical quality, including albumen height, Haugh unit, and eggshell thickness, was optimized at 2% BST, whereas excessive inclusion compromised shell quality and egg weight. Egg composition was modestly affected, mainly in lipid and moisture contents, with interactions between diet and hen age. Sensory evaluation revealed that eggs from hens fed up to 1% BST maintained high acceptability, while higher inclusion levels negatively affected taste. The observed benefits at moderate inclusion levels are likely associated with the presence of highly digestible proteins, bioactive peptides, and fermentation-derived compounds that enhance nutrient utilization and productive efficiency. Conclusively, BST represents a viable and sustainable ingredient for laying hen diets when included at moderate levels (≤ 2%), providing a novel strategy for valorizing aquaculture by-products while optimizing productive performance, physiological responses, and egg quality, considering age-related adaptability.

Dispersal and Regional Diversification Reveal Tropical Mountain Systems as Cradles of Diversification for the Forking Ferns (Gleicheniaceae, Polypodiopsida) - Lucas Vieira Lima; Alexandre Salino; Michael Kessler; Germinal Rouhan; Weston Testo; André Luís de Gasper; Thaís Elias Almeida (Journal of Biogeography, 2026)
Aim To reconstruct the historical biogeography and diversification dynamics of the fern family Gleicheniaceae, testing whether (1) its main centres of diversity are the result of within‐area speciation or lineage immigration, (2) dispersal shows directionality across tropical regions and (3) shifts in geographic distribution are correlated with diversification rates. Location Tropical and subtropical regions worldwide, with a focus on tropical America and Southeast Asia. Taxon Fern family Gleicheniaceae (Polypodiopsida). Methods We used a time‐calibrated phylogeny of Gleicheniaceae combined with ancestral range reconstruction in BioGeoBEARS. Stochastic biogeographic mapping was used to estimate the frequency and directionality of biogeographic events. Diversification dynamics were evaluated using both constant‐rate (Yule and Birth–Death) and rate‐variable (BAMM) approaches, and their relationship with dispersal frequency was examined. Results Dispersal was consistently recovered as the predominant process shaping the distribution of Gleicheniaceae under the best‐fitting BAYAREALIKE+J model. Among dispersal‐related processes, range expansion was the most frequent biogeographic event, particularly between the Andes and Brazil, and between Asia and Oceania. Founder‐event dispersal contributed secondarily, enabling long‐distance colonisation. Within‐area cladogenetic events were also frequent, especially in Sticherus . Diversification rates varied across clades: Sticherus and Dicranopteris showed the highest net diversification, coinciding with Neogene peaks in dispersal and climatic changes, whereas geographically restricted genera ( Rouxopteris , Stromatopteris ) exhibited the lowest diversification rates. Main Conclusions The evolutionary history of Gleicheniaceae was dominated by dispersal, with the Andes and Asia representing important centres of lineage accumulation and redistribution within their respective regions. Dispersal directionality and its correlation with diversification highlight tropical montane systems as key drivers of lineage radiation. Although complementary analyses indicate that historical geographic isolation may also have contributed to deep divergences, the overall biogeographic pattern remained dominated by dispersal in this ancient fern lineage.

Enhancing water management and natural resource use in tropical grassland systems under semi-arid conditions: Dual Kc approach - Cleber Pereira Alves; Danielle da Silva Eugenio; Luciana Sandra Bastos de Souza; Alexandre Maniçoba da Rosa Ferraz Jardim; Carlos André Alves de Souza; Gabriel Italo Novaes da Silva; João Pedro Alves de Souza Santos; Wilma Roberta dos Santos; Álefe Chagas de Lima Costa; Leonardo Francelino de Souza; Jandis Ferreira Nunes de Araujo; Ênio Farias de Franca e Silva; et al. (Biomass and Bioenergy, 2026)

Genotype × environment interaction in a national network of common bean trials across the three cropping seasons in Brazil - Demila Duarte da Mata Cruz; Alexandre Bryan Heinemann; Paula Pereira Torga; Eduardo Almeida Alves; Rafael Tassinari Resende (Euphytica, 2026)
The cultivation of common bean in Brazil typically occurs in three annual cropping seasons across the country’s major geographic regions, exposing genotypes to contrasting environmental conditions across time (seasons and years) and space (locations). With this aim, this study investigated the influence of the G × E interaction on common bean yield across different sites, seasons, and years. It evaluated the contributions of fixed and random effects. Data from 424 multi-environment trials (METs) conducted by Embrapa between 2011 and 2018 were used, involving 87 genotypes across three cropping seasons (Wet, Dry, and Winter) distributed over 71 locations. Genetic and environmental effects were estimated through linear mixed models fitted with the REML/BLUP method. In addition, multivariate analyses, including the GGE Biplot, were used to decompose and visualize G × E effects, while missing data were imputed via Principal Component Analysis (PCA). Environmental stratification and the identification of mega-environments enabled grouping sites with similar characteristics based on the presence or absence of G × E interactions. The stability and adaptability analysis of the cultivars, based on a ranking that considered the particularities of the PRVG, MHPRVG, Lin and Binns, Wricke’s Wi, and Finlay–Wilkinson indices, revealed distinct patterns of behavior across the three seasons.

Peripheral microRNA signature in genetic frontotemporal dementia—findings from the GENFI initiative - Chiara Fenoglio; Maria Serpente; Marina Arcaro; Tiziana Carandini; Luca Sacchi; Manuela Pintus; Vittoria Borracci; Giulia Giudici; Marta Rigoni; Paola Muti; Laura Ghezzi; Arabella Bouzigues; et al. (GeroScience, 2026)
Frontotemporal dementia (FTD) is a neurodegenerative disease characterized by significant clinical and genetic heterogeneity, with approximately 40% of cases linked to hereditary genetic mutations, including MAPT , GRN , and C9ORF72 . Recently, microRNAs (miRNAs) have emerged as key regulators of cellular processes related to neurodegeneration and as potential biomarkers for FTD. However, their relevance in presymptomatic stages remains poorly understood. We conducted a miRNA expression analysis using TaqMan OpenArray® panels on blood samples collected from 171 individuals, including symptomatic mutation carriers (SMC), presymptomatic carriers (PMC), and healthy non-carriers (NC). Dysregulated miRNAs were validated and bioinformatic tools were used to identify potential associated molecular pathways. In C9ORF72 , miR-20b-5p and miR-223-5p were significantly upregulated in SMC (fold regulation over NC: 2.418 p = 0.0336 and 7.829 p < 0.0264 respectively) and PMC (5.518, p < 0.0001 and 3.941, p < 0.0001 respectively). In GRN mutation carriers, miR-28-3p was altered in both SMC and PMC (fold regulation over NC: 1.484 p < 0.050 and 3.287, p < 0.050). In MAPT mutation carriers, miR-28-5p, miR-192-3p, miR-25-3p, and miR-532-3p were altered only in SMC (fold regulation over NC: 1.496 p < 0.050, 1.911 p = 0.006, 1.468 p < 0.05, and 0.728 p < 0.05). Bioinformatic analysis revealed enrichment of pathways related to neurodegeneration and synapse impairment. These results suggest that miRNA expression levels are deregulated in mutated SMC, in C9ORF72 and GRN PMC. Notably, miR-20b-5p, miR-223-5p, and miR-28-3p were increased in preclinical stages of the disease, supporting their role as early biomarkers for C9ORF72 -FTD and GRN -FTD. Conversely, alterations in MAPT carriers appeared only in symptomatic stages, suggesting a different involvement in disease progression.

Parental autonomy-supportive food practices and fruit and vegetable consumption in children: A systematic review and meta-analysis - Elisama Costa Lopes; Priscylla Rodrigues Vilella; Paula Ruffoni Moreira; Sarah Warkentin; Alexandre Siqueira Guedes Coelho; Géssica Mercia de Almeida; Matias Noll; Raquel Machado Schincaglia; Karine Anusca Martins (Appetite, 2026)

Assessment of toxic and potentially toxic elements in fishery species in the southeastern region of Brazil: Environmental correlations, biometrics, and human health risk - Paloma de Almeida Rodrigues; Arlen Carvalho de Oliveira Almeida; Alexandre Mendes Ramos-Filho; Bernardo Ferreira Braz; Ricardo Erthal Santelli; Carlos Adam Conte-Junior (Marine Pollution Bulletin, 2026)

Morphological characterization and distribution of antennal sensilla on Thyrinteina arnobia (Stoll, 1782) (Lepidoptera: Geometridae) - Elmadã Pereira Gonzaga; Camila Alexandre Cavalcante de Almeida; Lucas Teles Bezerra; Maclauds Nathan Feliciano Salmento; Fernanda da Silva Gonçalves; Henrique Fonseca Goulart; Antônio Euzébio Goulart Santana; Johnnatan Duarte de Freitas; Mariana Oliveira Breda (Zoologischer Anzeiger, 2026)

Semi-synthesis of sodium copper chlorophyllin from Chlorella vulgaris cultivated under continuous photoperiod and sequential extraction of fatty acids and exopolysaccharides - Jamila Sueira de Jesus Silva; Fábio Alexandre Chinalia; Carolina Oliveira de Souza; Denilson de Jesus Assis; Jania Betânia Alves da Silva; Gabriele Marques dos Santos; Fernanda Teixeira Cruz; Ravena Maria de Almeida Medeiros; Paulo Vitor França Lemos; Lucas Guimarães Cardoso (Food and Bioproducts Processing, 2026)

Beyond the green: Socioeconomic and climatic pressures on native vegetation in the Araguaia biodiversity corridor - Marco Aurélio Mendes Elias; José Alexandre Diniz-Filho; Natália Mundim Tôrres; Renato Alves Moreira; Giselle Bastos Alves; Anah Teresa de Almeida Jácomo; Leandro Silveira (Environmental Development, 2026)

First or best? Contrasting approaches reveal different outcomes in tadpole (Hypsiboas lundii) escape performance under acute chlorpyrifos exposure - David Sánchez-Domene; Alba Navarro Lozano; Alexandre Vidotto Barboza Lima; Camila Nomura Pereira Boscolo; Amanda Huga Magrini; Eduardo Alves de Almeida (Behavioural Processes, 2026)

A green approach to Azo dye C.I. Disperse blue 291 treatment: mitigating ecotoxicological effects through enzymatic and adsorptive strategies using endophytic fungi - Esperança Edna Alexandre Chibite; Débora Elisa Antunes de Mendonça; Mariane Aparecida Franco de Godoy; Adriane do Nascimento; João Artur dos Santos Oliveira; Brian Alvarez Ribeiro de Melo; Michele Cristina Heck; Julio Cesar Polonio; Igor Vivian Almeida; Veronica Elisa Pimenta Vicentini (World Journal of Microbiology and Biotechnology, 2026)

Fights in a tight space: wax scale Ceroplastes deodorensis Hempel (Hemiptera: Coccidae: Ceroplastinae) and associated parasitoids (Hymenoptera: Chalcidoidea) on a new host plant (Arecaceae) - Nyeppson de Sousa Soares; Anne Caroline Santos Küll; Alexandre Santos Araújo; Gabriel Silva Dias; Ana Lúcia Benfatti Gonzalez Peronti; Leonardo Souza Duarte; Bianca Mendes de Almeida; Yanka Silva de Sousa; Valmir Antonio Costa; Roberto Antonio Zucchi; Marcoandre Savaris (International Journal of Tropical Insect Science, 2026)
The hosts of Ceroplastes deodorensis Hempel (Hemiptera: Coccidae) belong to the families Annonaceae and Moraceae, which are exclusively recorded in Brazil. In this report, we document for the first time the occurrence and impact of C. deodorensis on adult plants of the dwarf date palm, Phoenix roebelenii O’Brien (Arecaceae), in Brazil. The wax scale was collected and examined on P. roebelenii at the “Luiz de Queiroz” campus in Piracicaba, São Paulo, Brazil, between April 2024 and March 2025. The population of C. deodorensis peaked from April to October 2024, causing damage solely to the leaves (leaflets) of the dwarf date palm, which manifested as yellowing and drying. The scale insect was found to be parasitized by four species of Chalcidoidea from four families: Aprostocetus sp. (Eulophidae), Brasema sp. (Eupelmidae), Metaphycus floridensis Santos & Tavares (Encyrtidae) (new record), and Scutellista caerulea (Fonscolombe) (Eunotidae) (new record). Notably, M. floridensis and S. caerulea comprised over 90% of the total parasitoids collected. This study serves to compile and update information regarding the hosts and parasitoids of C. deodorensis.

Landfill gas loading ramp-up strategies: Acclimatization optimization and long-term oxidation capacity of methane oxidation biosystems - Jessica Leindorf de Almeida; Jacopo De Tommaso; Federico Galli; Alexandre Cabral (Waste Management, 2026)

Greywater use in anaerobic digestion of cattle manure: Advancing biogas yield, energy efficiency, and digestate valorization for environmental sustainability in semi-arid regions - Daniela Silva Gomes Moreira do Valle; Marcélio Alves Teotônio; Jadde Milena Guedes Secundino; Tassia Cristina da Silva; Elisabete Albuquerque dos Santos Benvenuto; Allan Almeida Albuquerque; Bárbara Ribeiro Alves Alencar; Alexandre Nunes da Silva; Sergio Peres; Rejane Rodrigues da Costa e Carvalho; Emmanuel Damilano Dutra; Rômulo Simões Cezar Menezes (Science of The Total Environment, 2026)

Membrane-targeted photodynamic mechanisms of methylene violet 3RAX in melanoma models - Thais Soares de Oliveira; Mirella Boaro Kobal; André Satoshi Ferreira; Alexandre Mendes de Almeida Junior; Karina Alves Toledo; Sabrina Aléssio Camacho; Pedro Henrique Benites Aoki (Journal of Photochemistry and Photobiology B: Biology, 2026)

Evaluating an isotopic model for tracing the geographic origin of soybeans in Brazil - Maria Gabriella da Silva Araújo; Deoclecio Jardim Amorim; Rodrigo Figueiredo Almeida; Edmar Mazzi; Ana Claudia Gama Batista; Isabela Maria Souza-Silva; Alexandre Tadeu Brunello; Gabriela Bielefeld Nardoto; Gabriel J. Bowen; Luiz Antonio Martinelli (Food Chemistry, 2026)

Tandem Nutrient and Ripener Application Improves the Yield and Quality of Middle and Late Harvest Sugarcane - Anibal Pacheco de Almeida Prado Filho; Cleber de Morais Hervatin; Letusa Momesso; Lucas Moraes Jacomassi; Marcela Pacola; Carlos Alexandre Costa Crusciol (Sugar Tech, 2026)

Correction: Functional diversity of Brazilian bees: revealing the unique patterns of the Neotropics - Guaraci D. Cordeiro; Tereza C. Giannini; Patrick M. Consorte; Ana C. J. Costa; Waira S. Machida; Bruno F. Marques; Nicholas D. Mazzei; Poliana P. Menezes; Ludmila S. Resende; Juliana A. Shimoda; Renata S. Souza; André L. Acosta; et al. (Oecologia, 2026)

Deep learning-enhanced QSAR modeling for predicting developmental neurotoxicity based on molecular initiating events from adverse outcome pathways - Eufrásia de Sousa Pereira; Vinícius Alexandre Fiaia Costa; Eder Soares de Almeida Santos; Bruno Junior Neves (Molecular Diversity, 2026)
Developmental neurotoxicity (DNT) is linked to chemical exposure that disrupts the nervous system in humans or animals. Traditional methods for assessing chemical toxicity are valuable but often time-consuming, costly, and involve significant animal use, making it impractical to meet growing demands. To address this, we developed a deep learning-enhanced QSAR modeling framework aimed at predicting binding affinities towards molecular initiating events (MIEs) and key events (KEs) within the Adverse Outcome Pathway (AOP) relevant to exposure to pesticide-contaminated cannabis. Our model was trained on data from 24,476 compounds, sourced from the ChEMBL database, and tested against 4 MIE and 6 KE tasks. The DNNs showed superior performance, with an average correlation coefficient of 0.82 ± 0.05 and a root mean square error of 0.72 ± 0.08 for the test set. To enhance interpretability, we used SHAP values to explain the model’s predictions clearly. Furthermore, ECFP4 feature contributions were mapped onto known neurotoxic compounds to highlight regions likely responsible for MIEs visually. Our results confirm that developed models accurately predict DNT and effectively identify the correct MIEs and KEs for several neurotoxicants. Graphical abstract

First report of Penicillium digitatum causing postharvest rot in lemon in Brazil - Glícia Silva de Moraes; Amanda Cupertino de Queiroz Brito; Ana Elisa de Almeida Souza; Jordana Alves da Silva Melo; José Vitorino da Silva Neto; Cristina Maria de Souza-Motta; Alexandre Reis Machado (Journal of Plant Pathology, 2026)

Satellite evidence for persistent degradation in Brazil's desertification nuclei - Alanderson Firmino de Lucas; Marcos Vinícius da Silva; Alexandre Maniçoba da Rosa Ferraz Jardim; Luciana Sandra Bastos de Souza; Gabriel Thales Barboza Marinho; Lady Daiane Costa de Sousa Martins; João Emanoel Ambrósio Gomes; Gledson Luiz Pontes de Almeida; Jhon Lennon Bezerra da Silva; Wilma Roberta dos Santos; Wagner Martins dos Santos; Elania Freire da Silva; et al. (Remote Sensing Applications: Society and Environment, 2026)

Variability in the pore structure of microbialites in Lagoa Salgada: Implications for reservoir characterization and petrophysical interpretations - Tales Rodrigues de Almeida; Mateus Basso; Guilherme Furlan Chinelatto; Eddy Ruidiaz Munoz; Alexandre Campane Vidal (Journal of South American Earth Sciences, 2026)

Enhancing productivity in growing rabbits: the impact of lipid source supplementation - Alexander Alexandre de Almeida; Jean Kaique Valentim; Joyce Zanella; Orlando Filipe Costa Marques; Janaina Tayna Silva; Leonardo da Silva Fonseca; Andrea Maria de Araújo Gabriel; Euclides Reuter de Oliveira (Tropical Animal Health and Production, 2026)

Functional diversity of Brazilian bees: revealing the unique patterns of the Neotropics - Guaraci D. Cordeiro; Tereza C. Giannini; Patrick M. Consorte; Ana C. J. Costa; Waira S. Machida; Bruno F. Marques; Nicholas D. Mazzei; Poliana P. Menezes; Ludmila S. Resende; Juliana A. Shimoda; Renata S. Souza; André L. Acosta; et al. (Oecologia, 2026)
Bees are essential for ecosystem functioning, pollinating many wild and crop plant species. Predicting which species are most vulnerable to global changes, and how their loss may impact ecosystems and human well-being, is critical. Comprehensive information on bee response and effect traits is fundamental to these assessments. However, the Raunkiærian shortfall—insufficient trait data—remains significant for bees, particularly in the Neotropics. Moreover, it remains uncertain whether conservation strategies based on functional diversity from temperate regions can be generalized to the Neotropics. To address this gap, we compiled a comprehensive and validated dataset on Brazilian bee traits, covering 24 traits related to sociality (100% of the species with some information), nesting (88%), body size (71%), and buzzing capacity (42%) on 2,066 Brazilian bee species. The trait data here presented is a crucial resource for evaluating bee species' pollination effectiveness and susceptibility to global change. Comparative analysis with regions with ample trait data—USA, Europe, and China—revealed notable differences. Brazilian bees exhibited a higher prevalence of aboveground nesting species, especially compared to Europe. The proportion of eusocial species was also greater than in Europe and the United States, and more similar to China. Differently from other regions, Brazilian eusocial bees were significantly smaller than their non-eusocial counterparts. These cross-regional comparisons highlight the importance of geographically tailored conservation strategies and underscore the need for extensive trait data to accurately predict regional vulnerabilities and ecological impacts in a rapidly changing world.

Size-niche specific processes between mero- and holoplankton stabilize the continuum in size spectra of tropical estuarine and marine ecosystems - Denise Fabiana de Moraes Costa Schwamborn; Catarina da Rocha Marcolin; Nathália Lins-Silva; Morgana Brito-Lolaia; Alexandre Oliveira Almeida; Ralf Schwamborn (Journal of Marine Systems, 2025)

Characterization of the physicochemical, nutritional and mineral composition of Curriola (Pouteria ramiflora) and Marmelada bola (Alibertia edulis) pulp, peel and seed at different maturation stages - Maria da Graça Tomás; Carlos Alexandre Rocha da Costa; Hanna Elisia Araújo de Barros; Caio Vinicius Lima Natarelli; Luíz Guilherme Malaquias da Silva; Elisangela Elena Nunes Carvalho; Katiuchia Pereira Takeuchi; Flávia Matias Oliveira da Silva; Eduardo Valério de Barros Vilas Boas; Francisco de Almeida Lobo; Luiz José Rodrigues (Food and Humanity, 2025)

Monitoring soil conservation techniques via UAV for sustainable production of intercropped forage cactus with reuse water in the Brazilian semiarid region - Lizandra de Barros de Sousa; Abelardo Antônio de Assunção Montenegro; Jorge Manuel G.P. Isidoro; Thieres George Freire da Silva; Thayná Alice Brito Almeida; João Luis Mendes Pedroso de Lima; Pedro Rogério Giongo; Alexandre Maniçoba da Rosa Ferraz Jardim; Marcos Vinícius da Silva; Ênio Farias de França e Silva; Breno Leonan de Carvalho Lima (Field Crops Research, 2025)

Catastrophic wildfires in the Pantanal wetlands as catalysts for transformative change - Alexandre de Matos Martins Pereira; Geraldo Alves Damasceno-Junior; Renata Libonati; Liana O. Anderson; Allan Henrique de Almeida Souza; Bruno Henrique dos Santos Ferreira; Andre Valle Nunes; André Luiz Siqueira; Angelica Guerra; Angelo Cipriano Pacelli Rabelo; Arnaud L.J. Desbiez; Arthur Henrique Leite Falcette; et al. (Environmental Science & Policy, 2025)

Flood-Fire Interplays in Wetlands: The Rising of an Actionable Field of Study - Geraldo Alves Damasceno-Junior; Alexandre de Matos Martins Pereira; Bambang Hero Saharjo; Sally Archibald; Beibei Zhang; Bibiana Bilbao; Bruno Henrique dos Santos Ferreira; Carol Kagaba Kairumba; Danilo Bandini Ribeiro; David G. Campbell; Denis Mburu Njoroge; Dennis Twinomujuni; et al. (Wetlands, 2025)
Floods and fires are part of the ecological regime in many wetlands, yet their interconnectedness is poorly explored. Climate extremes, such as droughts and heatwaves, are increasing fire frequency and intensity, while changing rainfall patterns make floods more unpredictable. These events shape wetland physiognomy, species composition, and functioning. Different wetlands experience varying fire exposure; seasonally inundated grasslands burn almost annually, whereas tropical forests rarely catch fire. Some wetlands are more resilient to fire, drought, and floods than others. Communities dependent on wetlands possess ecological knowledge that supports adaptation, enhancing ecosystem resilience. Though often studied separately, floods and fires in wetlands are interrelated. In addition to environmental aspects, social, cultural and associated traditional knowledge dimensions must be included in conservation processes for these environments. A holistic understanding is crucial for conservation. Researchers from sixteen countries propose a new field of study on flood-fire interactions to improve wetland management and sustainability.

Soil–climate interactions drive above-ground biomass in the Caatinga, the largest Neotropical seasonally dry tropical forest - Alexandre T. Brunello; Domingos Cardoso; Peter W. Moonlight; Ítalo A. C. Coutinho; John Cunha; Mário M. do Espírito Santo; Magna S. B. de Moura; Luciano P. de Queiroz; Rubens M. dos Santos; Tiina Särkinen; Raquel C. Miatto; Tony C. de S. Oliveira; et al. (Plant and Soil, 2025)

Correspondence to “Exploring the impact of exercise induced BDNF on neuroplasticity in neurodegenerative and neuropsychiatric conditions” [Molecular Biology Reports (2025) 52:140] - Alexandre Aparecido de Almeida; Ricardo Mario Arida (Molecular Biology Reports, 2025)

A novel case of feline Exophiala spinifera disease in Americas: review integrating diagnosis and clinical - Mariana Almeida Ferreira; Gabrielle Silveira Vargas; João Vitor Gregolan Barbosa; Allana de Paula Castilho; Ingrid Gonçalves Costa Leite; Jandra Pacheco dos Santos; Marina Pacheco Miguel; Tiago Alexandre Cocio; Roseli Santos de Freitas-Xavier; Álvaro Ferreira Júnior (Brazilian Journal of Microbiology, 2025)

Experimental assessment of beauvericin toxicity in tadpoles of Dendropsophus minutus (Anura: Hylidae) - Monica Chacon de Vicente; Luiza Gabriella Ferreira de Paula; Renata Maria Pereira de Freitas; Adieli dos Anjos Almeida; Diego da Silva Lima; Rebeca dos Santos Gabriel; Nathany Geraldino Nogueira; Nádya Raquel dos Santos Batista; Alexandre Có Mangoni Barros; Marcelino Benvindo de Souza; Rogério Pereira Bastos; Pedro Vale de Azevedo Brito; et al. (Toxicon, 2025)

Sustainable agriculture with cyanobacterial biomass: Soil experiments on spinach and radish plants - Anabella Massa; Diogo Martins; Joana Azevedo; Ana I. Prieto; Ana M. Camean; Leticia Diez-Quijada; Angeles Jos; Mariana Reimão; Rui Azevedo; Edgar Pinto; Agostinho Almeida; Vitor Vasconcelos; et al. (Science of The Total Environment, 2025)

Exposure to bisphenol S promotes renal damage via aryl hydrocarbon receptor and NF-κB pathways in a mice model of obesity - Michele Lima Brito; Joana Ramos de Araujo; Patricia Pereira Almeida; Beatriz Alexandre-Santos; Beatriz Gouvêa de Luca; Kauet de Matos Gama e Souza; Denise Pires de Carvalho; Denise Mafra; Eliete Dalla Corte Frantz; Clarice Machado-Santos; Leandro Miranda-Alves; D'Angelo Carlo Magliano; et al. (Environmental Research, 2025)

Myiasis-causing flies in anurans: new interactions, geographic distribution, and an updated list of records in the Neotropics - Franciele Cristina de Souza; Victor Morais Ghirotto; Alexandre Polletini Neto; Camila Saraiva dos Anjos; André Luís F. da Silva; Rodrigo Lingnau; Emeline da S. Ceccon; Cátia Antunes de Melo-Patiu †; Mirco Solé; Silionamã P. Dantas; Claudio Borteiro; Domingos de J. Rodrigues; et al. (Biologia, 2025)

Malassezia pachydermatis sensitivity to plant extracts from the Brazilian Amazon Rain Forest - Ivana Barbosa Suffredini; Jefferson de Souza Silva; Sergio Alexandre Frana; Karen Cristina Comin Maldonado; Mateus Luís Barradas Paciencia; Liv Nunes Almeida Gomes; Marcelo Henrique Soller Ramada; Antonio Drauzio Varella (Phytochemistry Letters, 2025)

Sensor detection of shelf life: a multi-technique food analytical platform for mushroom analysis - Patricia Yukari Saiki; Fernando Cesar Rufino; Cassio Roberto de Almeida; Geovana Manzan Sales; Arthur Noin de Oliveira; Dunieskys Roberto Gonzalez Larrude; Ricardo Cotrin Teixeira; José Alexandre Diniz; Rodrigo Ramos Catharino (Food Research International, 2025)

Screening for Viruses in Pallas’s Long-Tongued Bats (Glossophaga soricina) in Brazil - Alexandre Sita; Gabriela E. Birlem; Deivid S. da Silva; Larissa Mallmann; Meriane Demoliner; Mariana S. da Silva; Juliana S. Gularte; Vyctoria M. A. G. Pereira; Paula R. de Almeida; Alana W. Hansen; André A. Witt; Juliane D. Fleck; et al. (Journal of Molecular Evolution, 2025)

Genomic selection in Passiflora breeding for CABMV resistance and agronomic performance - Débora Souza Mendes; Alexandre Pio Viana; Flavia Alves da Silva; Natan Ramos Cavalcante; Joameson Antunes Lima; Janeo Eustáquio de Almeida Filho; Orzenil Bonfim da Silva Júnior; Dario Grattapaglia (Euphytica, 2025)

Emergy accounting of surplus food donation: Health Co-benefits and environmental implications using CEAGESP (Brazil) as a case study - Federico Sulis; Feni Agostinho; Alexandre Souza; Cecília M.V.B. Almeida; Biagio F. Giannetti (Journal of Cleaner Production, 2025)

On the importance of digital soil mapping scale for ecosystem service assessment and policy - A study involving soil sediments dynamic and direct aquifer recharge - Fernanda Almeida Bócoli; Junior Cesar Avanzi; Bruno Montoani Silva; Vanêssa Lopes de Faria; Maria Cecília Vieira Totti; Michele Duarte de Menezes; Alexandre Uezu; Nilton Curi; Sérgio Henrique Godinho Silva (Geoderma Regional, 2025)

Impact of chitosan-based oleogels crosslinked with vanillin containing different oil phases on lipid digestion and bioaccessibility of carotenoids and tocols - Jorge da Silva Pinho-Jr; Bruno Saud Moreira; Gabriela Baptista Brito; Leticia Gonçalves de Almeida Torres; Débora Nascimento Eiriz; Alexandre Guedes Torres; Anderson Junger Teodoro; Daniel Perrone; Vanessa Naciuk Castelo-Branco (Food Chemistry, 2025)

Flexural behavior of steel and polypropylene fiber-reinforced concrete beams with low longitudinal reinforcement ratios - Darwin La Torre Esquivel; Flávio de Andrade Silva; Alexandre Almeida Del Savio (Engineering Structures, 2025)

Biochar Application to Recover Degraded Soils: Comparison of Different Biomass Sources Assessed by Soil Physical Quality and Maize Growth - Tiago da Costa Dantas Moniz; João Marcos Rodrigues dos Santos; Gilvanete da Silva Henrique; Francisco Luan Almeida Barbosa; João Ivo Rodrigues de Sousa; Ícaro Vasconcelos do Nascimento; Alexandre dos Santos Queiroz; Carlos Tadeu dos Santos Dias; Maria Vitória Ricarte Gonçalves; Mirian Cristina Gomes Costa; Helon Hébano de Freitas Sousa; Francisca Gleiciane da Silva; et al. (Journal of Soil Science and Plant Nutrition, 2025)

Metabolic brain changes in post-acute COVID-19: systematic review and meta-analysis of [18F]-FDG-PET findings - Izabella Fernanda Bastos Siqueira; Lais Almeida Figueiredo; Camila Emanuele Moreira Fernandes; Leandro Pinheiro Cintra; Glauber Fernandes de Oliveira; Maria Angélica Rios; Ricardo Maciel; Rodrigo Ferretjans; Nathalia Sernizon Guimarães; Luiz Alexandre Viana Magno (Brain Structure and Function, 2025)

Indigenous land is the keystone to protecting Brazilian bat (Mammalia: Chiroptera) biodiversity and their ecosystem services - Bruna Nascimento de Oliveira; Rafaela Jemely Rodrigues Alexandre; Simone Almeida Pena; Letícia Lima Correia; Allysson Moura Luz; Thiago Bernardi Vieira (Biological Conservation, 2025)

Comparison of the nephroprotective effect of [6]-gingerol and the [6]-gingerol-β-cyclodextrin complex against cisplatin-induced AKI - Dayara de Oliveira Silva; Mikael Almeida Lima; Thiago Miranda de Freitas; Francisco Cleber Silva Ferreira; Antônio Klingem Leite de Freitas; Mário Rogério Lima Mota; James Almada da Silva; Marco Antonio de Freitas Clementino; Alexandre Havt (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

Stable isotopic differences ( δ 13 C and δ 15 N ) between muscle and fin ray tissues from juvenile Atlantic goliath grouper Epinephelus itajara (Lichtenstein, 1822) using non‐lethal sampling - Ester F. Barbosa; Rodrigo F. Bastos; Lorena L. Almeida; Rafael L. Oliveira; Sabrina R. Vollrath; Alexandre M. Garcia; Mauricio Hostim‐Silva; Mario V. Condini (Journal of Fish Biology, 2025)
The Atlantic goliath grouper ( Epinephelus itajara ) is the largest species of grouper in the Atlantic Ocean and is classified as critically endangered in Brazil. This study compared the isotopic ratios of carbon (δ 13 C) and nitrogen (δ 15 N) between the muscle tissue and dorsal‐fin rays of 37 juveniles to assess fin rays as a non‐lethal alternative to muscle tissue sampling. The δ 13 C values in rays were significantly higher than those found in muscle, whereas the δ 15 N values did not differ significantly between tissues. Both stable isotopes showed high Spearman correlation coefficients (>0.80) between tissues. Thus, the study can enhance future research and broaden the application of stable isotope techniques in a non‐lethal manner.

Response of methane oxidation biosystems to controlled ingress of oxygen - Jessica Leindorf de Almeida; Jeovana Jisla das Neves Santos; Alexandre R. Cabral; Federico Galli (Waste Management, 2025)

Evaluation of web post-buckling in high-strength cellular steel and high-strength concrete composite beams: A numerical study - Jonas Yoshihiro Namba; Igor Eduardo da Silva Ribeiro; Haron Cesar Almeida Tavares; Alexandre Rossi; Pablo Augusto Krahl; Carlos Alberto Benedetty Torres; Carlos Humberto Martins (Engineering Structures, 2025)

Mulching in irrigated forage cactus promotes early harvest and improves the economic indices of the crop - Thieres George Freire da Silva; Renan Matheus Cordeiro Leite; Cleber Pereira Alves; George do Nascimento Araújo Júnior; Alexandre Maniçoba da Rosa Ferraz Jardim; Carlos André Alves de Souza; José Edson Florentino de Morais; Maria Madalena Lima de Barros; Jandis Ferreira Nunes de Araújo; Vinícius Santos do Nascimento; Alexsandro Claudio dos Santos Almeida; Hugo Rafael Bentzen Santos; et al. (Irrigation and Drainage, 2025)
To mitigate the negative effects of climate, the use of resilient agriculture is essential. This study evaluated the impact of different levels of biotic mulch on irrigated forage cactus yield, phenology and economic indices. The ‘Orelha de Elefante Mexicana’ clone was used and subjected to four levels of biotic mulch—BM (0, 5, 10 and 15 Mg ha −1 ) in a randomised block design with four repetitions. The treatments consisted of growing forage cactus with 0, 5, 10 and 15 Mg ha −1 mulch. The experiment was carried out in a semi‐arid environment in Brazil (Serra Talhada, Pernambuco State) over two successive cycles (August 2020 to August 2022). The yield, cutting time, and morphophysiological, economic and water use indicators were evaluated. There was no effect of the BM level on the final forage yield. In the first experimental cycle, the treatment with 10 Mg ha −1 BM brought the cutting time forward by 103°C day. The application of 15 Mg ha −1 BM prolonged phenophase 2, causing an increase of 236°C day in the cycle compared with the treatment with 10 Mg ha −1 BM. We concluded that mulch improved crop water and economic indicators, contributing to sustainable forage production in semiarid environments.

Combined effects of land use and geology on potentially toxic elements contamination in lacustrine sediments from the Araguaia River floodplain, Brazilian Savanna - Lucas Cabrera Monteiro; Ludgero Cardoso Galli Vieira; José Vicente Elias Bernardi; Thiago Aluisio Maciel Pereira; Walkimar Aleixo da Costa Júnior; Wesley Pinheiro da Silva; Leonardo Almeida Guerra dos Santos; José Francisco Gonçalves Júnior; João Carlos Nabout; José Alexandre Felizola Diniz Filho; Jeremie Garnier; Cleber Lopes Filomeno; et al. (Environmental Monitoring and Assessment, 2025)

Fecundity of the snapping shrimp Alpheus estuariensis (Caridea: Alpheidae) after the oil spill in three mangroves of tropical Brazil - Aline Santos Rios; Gabriel Lucas Bochini; Gilvan Takeshi Yogui; Emanuelly Pauliny Modesto; Alexandre Oliveira Almeida; Jesser F. Souza-Filho (Marine Pollution Bulletin, 2025)

Low carbon footprint of Nile tilapia farming with recirculation aquaculture - Anderson M. de Melo Júnior; Sarian Kosten; Vitor Luis da C. Duque; Alexandre A.O. Santos; André M. Amado; Laís C. Soranço; Jochem Dreise; Arthur C. Martins; Jonas Nasário; Ana Paula Dalbem Barbosa; Ive S. Muzitano; Giovana M. Cardoso; et al. (Resources, Conservation and Recycling, 2025)

BioTIME 2.0: Expanding and Improving a Database of Biodiversity Time Series - Maria Dornelas; Laura H. Antão; Amanda E. Bates; Viviana Brambilla; Jonathan M. Chase; Cher F. Y. Chow; Ada Fontrodona‐Eslava; Anne E. Magurran; Inês S. Martins; Faye Moyes; Alban Sagouis; Samuel Adu‐Acheampong; et al. (Global Ecology and Biogeography, 2025)
Motivation Here, we make available a second version of the BioTIME database, which compiles records of abundance estimates for species in sample events of ecological assemblages through time. The updated version expands version 1.0 of the database by doubling the number of studies and includes substantial additional curation to the taxonomic accuracy of the records, as well as the metadata. Moreover, we now provide an R package (BioTIMEr) to facilitate use of the database. Main Types of Variables Included The database is composed of one main data table containing the abundance records and 11 metadata tables. The data are organised in a hierarchy of scales where 11,989,233 records are nested in 1,603,067 sample events, from 553,253 sampling locations, which are nested in 708 studies. A study is defined as a sampling methodology applied to an assemblage for a minimum of 2 years. Spatial Location and Grain Sampling locations in BioTIME are distributed across the planet, including marine, terrestrial and freshwater realms. Spatial grain size and extent vary across studies depending on sampling methodology. We recommend gridding of sampling locations into areas of consistent size. Time Period and Grain The earliest time series in BioTIME start in 1874, and the most recent records are from 2023. Temporal grain and duration vary across studies. We recommend doing sample‐level rarefaction to ensure consistent sampling effort through time before calculating any diversity metric. Major Taxa and Level of Measurement The database includes any eukaryotic taxa, with a combined total of 56,400 taxa. Software Format csv and. SQL.

Propionate consumption activates mitochondrial activity, methylcitrate cycle and promotes changes in the cell wall of the human pathogen Histoplasma capsulatum - Luiz Paulo Araújo Santos; Dayane Moraes; Leandro do Prado Assunção; Matthias Brock; Kassyo Lobato Potenciano da Silva; Andréa Rodrigues Chaves; Rafael Oliveira Martins; Mirelle Garcia Silva-Bailão; Célia Maria de Almeida Soares; Alexandre Melo Bailão (Fungal Biology, 2025)

Capture of gaseous and fine particulate pollutants emitted in the biomass post-combustion process - Maria Angélica Martins Costa; Alexandre Jorge Duarte de Souza; Bruna Sampaio Mello; Eliza Almeida de Oliveira; Lucas Freitas Oliveira; Geisa Albini; Arnaldo Sarti; Kelly Johana Dussán (Environmental Science and Pollution Research, 2025)

Effect of Seasonality on the Contamination of Mussels (Perna perna) and Swimming Crabs (Achelous spinimanus) by Essential and Toxic Metals and the Health Risks of the Consumer Population on the Southeast Coast of Brazil - Alexandre Mendes Ramos-Filho; Paloma de Almeida Rodrigues; Adriano Teixeira de Oliveira; Júlia Vianna da Anunciação de Pinho; Bernardo Ferreira Braz; Ricardo Erthal Santelli; Carlos Adam Conte-Junior (Biological Trace Element Research, 2025)

Organic carbon stocks across various land use systems in Sandy Ultisols and Oxisols in Brazil - Maria Cecília Vieira Totti; Yuri Lopes Zinn; Sérgio Henrique Godinho Silva; Bruno Montoani Silva; Fernanda Almeida Bócoli; Vanêssa Lopes de Faria; Andrés Olaya Montes; Salvador Francisco Acuña-Guzman; Alexandre Uezu; Laury Cullen Junior; Vinícius Ferreira Fernandes; Junior Cesar Avanzi (Geoderma Regional, 2025)

Microencapsulating Lacticaseibacillus rhamnosus GG by spray drying using pea protein, pectin, and tapioca flour: Probiotic viability, digestibility and thermal stability - Newton Carlos Santos; Raphael Lucas Jacinto Almeida; Shênia Santos Monteiro; Thalis Leandro Bezerra de Lima; Alexandre da Silva Lúcio; Lídia Paloma da Silva Nogueira; Yaroslávia Ferreira Paiva; Mailson Gonçalves Gregório; Ana Carla de Oliveira Brito; Luanna Amado da Silva; Douglas Vinicius Pinheiro de Figueiredo; Rosenildo dos Santos Silva; et al. (Food and Bioproducts Processing, 2025)

Comparative efficacy of commercial phytases on phosphorus availability for broilers - Rosa Aparecida Reis de Léo; Jean Kaique Valentim; Rafael de Sousa Ferreira; Thaisa Pereira de França; Artur Macedo Ribeiro; Kaique Moreira Gomes; Alexander Alexandre de Almeida; Arele Arlindo Calderano (Tropical Animal Health and Production, 2025)

A new genus of Mycosphaerellaceae associated with leaf spots in Philodendron sp. from the Brazilian Atlantic forest - Jordana Alves da Silva Melo; Eliude dos Santos Oliveira da Silva; Amanda Cupertino de Queiroz Brito; Juliana Ferreira de Mello; Ana Elisa de Almeida Souza; Cristina Maria de Souza-Motta; André Luiz Firmino; Alexandre Reis Machado (Mycological Progress, 2025)

New records of peppermint shrimps from northeastern Brazil support Lysmata lipkei as junior synonym of Lysmata dispar - Rodrigo Guéron; J. Antonio Baeza; Gabriel Lucas Bochini; Mariana Terossi; Alexandre Oliveira Almeida (Regional Studies in Marine Science, 2025)

Predicted bird extinctions shifts morphological diversity in a metropolitan region in Eastern Amazon - Victória de Nazaré Gama-Silva; Alexandre Aleixo; Bianca Darski-Silva; Rony Peterson Santos Almeida; Rogério R. Silva (Urban Ecosystems, 2025)

New reports of Rhizopus and Mucor (Mucorales, Mucoromycota) causing post-harvest rot in tropical fruits in Brazil - Ana Elisa de Almeida Souza; André Luiz Cabral Monteiro de Azevedo Santiago; Amanda Cupertino de Queiroz Brito; Jordana Alves da Silva Melo; Cristina Maria de Souza-Motta; Alexandre Reis Machado (Journal of Plant Diseases and Protection, 2025)

Domestic cat hepadnavirus genotype B is present in Southern Brazil - Alaíse Tessmann; Juliana Sumienski; Alexandre Sita; Larissa Mallmann; Gabriela Espíndola Birlem; Nilson Júnior da Silva Nunes; Camila Gottlieb Lupion; Juliana Schaeffer Eckert; Meriane Demoliner; Juliana Schons Gularte; Paula Rodrigues de Almeida; Fernando Rosado Spilki; et al. (Virus Genes, 2025)

Size as a determinant of robustness: Exploring sexual dimorphism in the size and shape of the snapping and cutting claws in Alpheus (caridea: Alpheidae) - Whandenson M. Nascimento; Allysson P. Pinheiro; Alexandre O. Almeida (Zoologischer Anzeiger, 2025)

Biological silage from tambaqui (Colossoma macropomum) by-products on the productive performance, hematological parameters and egg quality of older commercial hens - Cristiane Cunha Guimarães; Tiago Cabral Nóbrega; Adriene Núzia de Almeida Santos; Alexandre Augusto Barai; Lígia dos Santos Mourão; Maria Fernanda da Silva Gomes; Wilson de Souza Ferreira; Francisco Alberto de Lima Chaves; Joel Lima da Silva Junior; Marco Antonio de Freitas Mendonça; Antônio José Inhamuns da Silva; João Paulo Ferreira Rufino; et al. (Tropical Animal Health and Production, 2025)

Detection of a novel hepacivirus in wild cavies (Cavia aperea aperea) - Gabriela Espíndola Birlem; Alexandre Sita; Juliana Schons Gularte; Deivid de Souza da Silva; Meriane Demoliner; Paula Rodrigues de Almeida; Juliane Deise Fleck; Fernando Rosado Spilki; Severino Silvano dos Santos Higino; Sergio Santos de Azevedo; Matheus Nunes Weber (Archives of Virology, 2025)

Integrative species delimitation and biogeography of the Rhinella margaritifera species group (Amphibia, Anura, Bufonidae) suggest an intense diversification throughout Amazonia during the last 10 million years - Antoine Fouquet; Miqueias Ferrão; Miguel T. Rodrigues; Fernanda P. Werneck; Ivan Prates; Leandro J.C.L. Moraes; Tomas Hrbek; Juan C. Chaparro; Albertina P. Lima; Renata Perez; Andre Pansonato; Vinicius T. Carvalho; et al. (Systematics and Biodiversity, 2024)

Corrigendum to “Antifouling activity and ecotoxicological profile of the cyanobacterial oxadiazine Nocuolin A” [Chemosphere 365 (2024), 143318] - Sandra Pereira; Isabel B. Oliveira; Maria Lígia Sousa; Catarina Gonçalves; Marco Preto; Maria V. Turkina; Vitor Vasconcelos; Alexandre Campos; Joana R. Almeida (Chemosphere, 2024)

Impact of dissolved/dispersed oil from a spill event on the development of embryos of the snapping shrimp Alpheus estuariensis (Caridea: Alpheidae) - Aline Santos Rios; Gilvan Takeshi Yogui; Marius Nils Müller; Alexandre Oliveira Almeida; Jesser F. Souza-Filho (Marine Pollution Bulletin, 2024)

Construction, monitoring, and efficiency of a biofilter treating a high flow, lean, landfill gas - Jessica Leindorf de Almeida; Joelle Dumouchel; Jeovana Jisla das Neves Santos; Yohan Dulac; Alexandre R. Cabral; Martin Héroux (Waste Management, 2024)

Declines in coastal macrozooplankton communities within a recent climate and ocean tipping point in the Tropical South Atlantic - Denise Fabiana de Moraes Costa Schwamborn; Catarina da Rocha Marcolin; Nathália Lins-Silva; Morgana Brito-Lolaia; Humberto L. Varona; Simone Maria de Albuquerque Lira; Alexandre Oliveira de Almeida; Ralf Schwamborn (Science of The Total Environment, 2024)

Trophic ecology and habitat use of an overexploited commercial snapper (Lutjanus jocu) in a tropical nursery estuary elucidated by stable isotopes - Patrick Derviche; Rodrigo F. Bastos; Mario V. Condini; Ester F. Barbosa; Rafael L. Oliveira; Lorena L. Almeida; Sabrina R. Vollrath; Marcelo Soeth; Alexandre M. Garcia; Maurício Hostim–Silva (Regional Studies in Marine Science, 2024)

Corrigendum to “Surviving the Tide: Assessing Guiana dolphin persistence amidst growing threats in a protected estuary in South-eastern Brazil” [J. Nature Conserv. 82 (2024) 126713] - Inaê Guion de Almeida; Alexandre Reis Percequillo; Mario Manoel Rollo (Journal for Nature Conservation, 2024)

Surviving the Tide: Assessing Guiana dolphin persistence amidst growing threats in a protected estuary in South-eastern Brazil - Inaê Guion de Almeida; Alexandre Reis Percequillo; Mario Manoel Rollo (Journal for Nature Conservation, 2024)

Arsenic, cadmium, and chromium concentrations in contrasting phosphate fertilizers and their bioaccumulation by crops: Towards a green label? - Mariana Rocha de Carvalho; Thiago Adorno de Almeida; Gustavo Avelar Zorgdrager Van Opbergen; Fábio Henrique Alves Bispo; Lívia Botelho; Alexandre Boari de Lima; Paulo Eduardo Ribeiro Marchiori; Luiz Roberto Guimarães Guilherme (Environmental Research, 2024)

Toxic and non-toxic cyanobacterial biomass as a resource for sustainable agriculture: A lettuce cultivation experiment - Anabella Massa; Érica Santos; Diogo Martins; Joana Azevedo; Mariana Reimão; Agostinho Almeida; Rui Azevedo; Edgar Pinto; Vitor Vasconcelos; Alexandre Campos; Marisa Freitas (Environmental Research, 2024)

Antibacterial activity of functionalized natural zeolites (NZ-AgNPs) and its application in bacteriological water treatment and commercial paints - Anna Carla Ribeiro; Alessandra Marjorie de Oliveira; Laiza Bergamasco Beltran; Alexandre Diório; Grace Anne Vieira Magalhães-Ghiotto; Benício Alves de Abreu Filho; Elizabeth da Costa Neves Fernandes de Almeida Duarte; Rosângela Bergamasco (Environmental Nanotechnology, Monitoring & Management, 2024)

Correction: Drug to genome to drug: a computational large-scale chemogenomics screening for novel drug candidates against sporotrichosis - Andressa Santana Santos; Vinícius Alexandre Fiaia Costa; Vivianny Aparecida Queiroz Freitas; Laura Raniere Borges dos Anjos; Eder Soares de Almeida Santos; Thales Domingos Arantes; Carolina Rodrigues Costa; Ana Laura de Sene Amâncio Zara; Maria do Rosário Rodrigues Silva; Bruno Junior Neves (Brazilian Journal of Microbiology, 2024)

The spermidine promotes maturation and tissue differentiation of somatic embryos of Euterpe edulis Martius, an endangered Atlantic Forest species - Joana Silva Costa; Tamyris de Mello; Débora Pellanda Fagundes; Tatiane Dulcineia Silva; Caroline Palacio de Araujo; Ingridh Medeiros Simões; Mariana Ribeiro de Almeida; Eduardo Santos Cade; João Pedro Vieira Fraga de Assis; Edilson Romais Schmildt; Wagner Campos Otoni; Amir Ali Khoddamzadeh; et al. (In Vitro Cellular & Developmental Biology - Plant, 2024)

Smart hotspot detection using geospatial artificial intelligence: A machine learning approach to reduce flood risk - Seyed MHS Rezvani; Alexandre Gonçalves; Maria João Falcão Silva; Nuno Marques de Almeida (Sustainable Cities and Society, 2024)

Disentangling the veil line for Brazilian biodiversity: An overview from two long-term research programs reveals huge gaps in ecological data reporting - Aretha Franklin Guimaraes; Luciano Carramaschi de Alagao Querido; Taina Rocha; Domingos de Jesus Rodrigues; Pedro Lage Viana; Helena de Godoy Bergallo; Geraldo Wilson Fernandes; Tiago Shizen Pacheco Toma; Helena Streit; Gerhard Ernst Overbeck; Alberico Queiroz Salgueiro de Souza; Albertina Pimentel Lima; et al. (Science of The Total Environment, 2024)

Effects of Plant Growth Regulators on Sugarcane Productivity and Quality of the Art Through the Increase in Photosynthetic and Antioxidant Activity - Cleber de Morais Hervatin; Anibal Pacheco de Almeida Prado Filho; Letusa Momesso; Lucas Morais Jacomassi; Carlos Alexandre Costa Crusciol (Journal of Plant Growth Regulation, 2024)

Antifouling activity and ecotoxicological profile of the cyanobacterial oxadiazine nocuolin A - Sandra Pereira; Isabel B. Oliveira; Maria Lígia Sousa; Catarina Gonçalves; Marco Preto; Maria V. Turkina; Vitor Vasconcelos; Alexandre Campos; Joana R. Almeida (Chemosphere, 2024)

Microwave-enhanced preparation of finned-FER zeolites and their application in the skeletal isomerization of FAME - Alexandre Ferreira Young; Pedro Nothaft Romano; Marco Aurélio Suller Garcia; Donato Alexandre Gomes Aranda; João Monnerat Araújo Ribeiro de Almeida (Fuel, 2024)

Proposal of a revision scale of the degree of cohesion and tensile strength to aid in the diagnosis of the cohesive character in soils - Angélica da Silva Lopes; Alexandre dos Santos Queiroz; Ícaro Vasconcelos do Nascimento; Lucas de Sousa Oliveira; Brivaldo Gomes de Almeida; José Coelho de Araújo Filho; Luciano da Silva Souza; Marlen Barros e Silva; Ricardo Espíndola Romero; Francisca Gleiciane da Silva; Mirian Cristina Gomes Costa; Jaedson Cláudio Anunciato Mota (CATENA, 2024)

Insights of potential trypanocidal effect of the synthetic derivative (2E)-1-(4-aminophenyl)-3-(2,4-dichlorophenyl)prop-2-en-1-one: in vitro assay, MEV analysis, quantum study, molecular docking, molecular dynamics, MPO analysis, and predictive ADMET - Márcia Machado Marinho; Matheus Nunes da Rocha; Emanuel Paula Magalhães; Lyanna Rodrigues Ribeiro; Caio Henrique Alexandre Roberto; Francisco Wagner de Queiroz Almeida-Neto; Marília Lopes Monteiro; João Victor Serra Nunes; Ramon Róseo Paula Pessoa Bezerra de Menezes; Emmanuel Silva Marinho; Pedro de Lima Neto; Alice Maria Costa Martins; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2024)

Drug to genome to drug: a computational large-scale chemogenomics screening for novel drug candidates against sporotrichosis - Andressa Santana Santos; Vinícius Alexandre Fiaia Costa; Vivianny Aparecida Queiroz Freitas; Laura Raniere Borges dos Anjos; Eder Soares de Almeida Santos; Thales Domingos Arantes; Carolina Rodrigues Costa; Ana Laura de Sene Amâncio Zara; Maria do Rosário Rodrigues Silva; Bruno Junior Neves (Brazilian Journal of Microbiology, 2024)

Evaluation of Seroprevalence and Risk Factors of Heartworm Infection for Dogs in Rio de Janeiro with Access to Veterinary Care - Mariana Guedes; Tamiris Gomes; Bruno Alberigi; Emilene Prudente; Alexandre Bendas; Thalita Souza; Flavya Mendes-de-Almeida; Fabiana Batalha Knackfuss; Alexandre Merlo; Norma Labarthe (Acta Parasitologica, 2024)
Heartworm infection is a chronic disease with clinical signs and effects ranging from an asymptomatic condition to severe disease and death. The prevalence of heartworm disease in the state of Rio de Janeiro has been reported to be high (21.3%). The present study was conducted to evaluate the seroprevalence and risk factors of heartworm infection for the canine population with access to veterinary services in different areas of the state of Rio de Janeiro, Brazil. A total of 1787 canine blood samples were obtained from 135 practices across 8 different areas of Rio de Janeiro state (Rio de Janeiro municipality, São Gonçalo municipality, Niterói municipality, Baixada Fluminense, and the northern, southern, eastern, and mountainous areas) and tested for the presence of Dirofilaria immitis antigens and antibodies against several tick-borne disease pathogens using a commercial immunochromatography technique (Vetscan® Flex 4 Rapid Test; Zoetis; NJ USA). Pet owners reported living conditions, physical characteristics, demographics, and clinical signs for evaluation of risk factors for heartworm infection. Only two evaluated risk factors were shown to enhance the risk for D. immitis infection, including having a short hair coat vs. having a medium or long hair coat (OR 2.62) or positive for antibodies to tick-borne disease parasites (OR 3.83). Clinical signs reported for dogs with heartworm disease were typical for that condition. The overall prevalence of heartworm disease in the state was 8.2%, ranging from 2.4% in the mountainous region to 29.4% in the eastern area. It could not be determined if veterinarians were not diligent about dispensing heartworm preventatives or if poor levels of compliance by dog owners were responsible for higher infection rates in some areas of the state.

Corrigendum: The Brazilian Santos basin underwater soundscape monitoring project (PMPAS-BS) - José Antonio Moreira Lima; William Soares Filho; Fabio C. Xavier; Thiago Pires de Paula; Angela Spengler; Fernando Gonçalves de Almeida; Diogo Peregrino Correa Pereira; Valéria Souza Rego; Cátia Galotta; Carlos Corrêa Junior; Alexandre Bazyl (Frontiers in Marine Science, 2024)

Evaluation of different supportive treatments during packed cell volume replacement in calves naturally infected with tick fever agents - Alexandre Braga Scarpa; Vanessa Ferreira Salvador; Luccas Lourenzzo Lima Lins Leal; Igor Maciel Lopes de Morais; Luiz Fellipe Monteiro Couto; Luciana Maffini Heller; Dina María Beltrán Zapa; Lídia Mendes de Aquino; Daniel de Castro Rodrigues; Nicolas Jalowitzki de Lima; Vando Edésio Soares; Lorena Lopes Ferreira; et al. (Veterinary Research Communications, 2024)

Histone 3 Trimethylation Patterns are Associated with Resilience or Stress Susceptibility in a Rat Model of Major Depression Disorder - Lucas Santos; Luiza Behrens; Camila Barbosa; Camila Tiefensee-Ribeiro; Helen Rosa-Silva; Nauana Somensi; Pedro Ozorio Brum; Alexandre Kleber Silveira; Matheus Scarpatto Rodrigues; Jade de Oliveira; Daniel Pens Gelain; Roberto F Almeida; et al. (Molecular Neurobiology, 2024)

Oil Spill Mitigation with a Team of Heterogeneous Autonomous Vehicles - André Dias; Ana Mucha; Tiago Santos; Alexandre Oliveira; Guilherme Amaral; Hugo Ferreira; Alfredo Martins; José Almeida; Eduardo Silva (Journal of Marine Science and Engineering, 2024)
This paper presents the implementation of an innovative solution based on heterogeneous autonomous vehicles to tackle maritime pollution (in particular, oil spills). This solution is based on native microbial consortia with bioremediation capacity, and the adaptation of air and surface autonomous vehicles for in situ release of autochthonous microorganisms (bioaugmentation) and nutrients (biostimulation). By doing so, these systems can be applied as the first line of the response to pollution incidents from several origins that may occur inside ports, around industrial and extraction facilities, or in the open sea during transport activities in a fast, efficient, and low-cost way. The paper describes the work done in the development of a team of autonomous vehicles able to carry as payload, native organisms to naturally degrade oil spills (avoiding the introduction of additional chemical or biological additives), and the development of a multi-robot framework for efficient oil spill mitigation. Field tests have been performed in Portugal and Spain’s harbors, with a simulated oil spill, and the coordinate oil spill task between the autonomous surface vehicle (ASV) ROAZ and the unmanned aerial vehicle (UAV) STORK has been validated.

Geography and ecology shape the phylogenetic composition of Amazonian tree communities - Bruno Garcia Luize; David Bauman; Hans ter Steege; Clarisse Palma‐Silva; Iêda Leão do Amaral; Luiz de Souza Coelho; Francisca Dionízia de Almeida Matos; Diógenes de Andrade Lima Filho; Rafael P. Salomão; Florian Wittmann; Carolina V. Castilho; Marcelo de Jesus Veiga Carim; et al. (Journal of Biogeography, 2024)
Aim Amazonia hosts more tree species from numerous evolutionary lineages, both young and ancient, than any other biogeographic region. Previous studies have shown that tree lineages colonized multiple edaphic environments and dispersed widely across Amazonia, leading to a hypothesis, which we test, that lineages should not be strongly associated with either geographic regions or edaphic forest types. Location Amazonia. Taxon Angiosperms (Magnoliids; Monocots; Eudicots). Methods Data for the abundance of 5082 tree species in 1989 plots were combined with a mega‐phylogeny. We applied evolutionary ordination to assess how phylogenetic composition varies across Amazonia. We used variation partitioning and Moran's eigenvector maps (MEM) to test and quantify the separate and joint contributions of spatial and environmental variables to explain the phylogenetic composition of plots. We tested the indicator value of lineages for geographic regions and edaphic forest types and mapped associations onto the phylogeny. Results In the terra firme and várzea forest types, the phylogenetic composition varies by geographic region, but the igapó and white‐sand forest types retain a unique evolutionary signature regardless of region. Overall, we find that soil chemistry, climate and topography explain 24% of the variation in phylogenetic composition, with 79% of that variation being spatially structured ( R 2 = 19% overall for combined spatial/environmental effects). The phylogenetic composition also shows substantial spatial patterns not related to the environmental variables we quantified ( R 2 = 28%). A greater number of lineages were significant indicators of geographic regions than forest types. Main Conclusion Numerous tree lineages, including some ancient ones (>66 Ma), show strong associations with geographic regions and edaphic forest types of Amazonia. This shows that specialization in specific edaphic environments has played a long‐standing role in the evolutionary assembly of Amazonian forests. Furthermore, many lineages, even those that have dispersed across Amazonia, dominate within a specific region, likely because of phylogenetically conserved niches for environmental conditions that are prevalent within regions.

Dereplication of polar extracts from Croton antisyphiliticus Mart. roots and its anti-inflammatory and antinociceptive potential - Jorge Luiz Souza Simão; Stephanie Vilela Prado; Alana Kelyene Pereira; Gerso Pereira Alexandre; Núbia Alves Mariano Teixeira Pires Gomide; Marcia Matos da Silva; Dionys de Souza Almeida; Aline Nazareth Martins; Daiany Priscilla Bueno da Silva; Elson Alves da Costa; Vanessa Gisele Pasqualotto Severino (Natural Product Research, 2024)

The Brazilian Santos basin underwater soundscape monitoring project (PMPAS-BS) - José Antonio Moreira Lima; William Soares Filho; Fabio C. Xavier; Thiago Pires de Paula; Angela Spengler; Fernando Gonçalves de Almeida; Diogo Peregrino Correa Pereira; Valéria Souza Rego; Cátia Galotta; Carlos Corrêa Junior; Alexandre Bazyl (Frontiers in Marine Science, 2024)
This paper describes the Santos Basin Underwater Soundscape Monitoring Project (PMPAS-BS), a Brazilian ocean soundscape monitoring initiative. The main objective of the project is to quantify and assess hydroacoustic noise of anthropogenic origin in a large sedimentary basin extending from 23° S to 28° S on the southeastern Brazilian continental margin of the South Atlantic Ocean. Noise associated with oil and gas (O&G) exploration and production activities is the primary target, but this oceanic region also has busy shipping lanes for commercial, military, and fishing vessels. The two main hubs of Brazil’s export and import of goods by sea are located in this region: Santos and Rio de Janeiro ports. The project has three measurement components: mobile monitoring based on gliders and drifting acoustic profilers, fixed shallow-water monitoring based on acoustic measurements at coastal stations near shipping lanes associated with exploration and production activities in the Santos Basin, and fixed oceanic monitoring based on deep-water mooring lines equipped with passive autonomous acoustic recorders near production units, shipping lanes, and areas with lower intensity of O&G activities (pristine or reference sites). Numerical modeling of anthropogenic underwater acoustic noise has also been included as a fourth project component. The PMPAS-BS covers an area of more than 251,000 km 2 and uses several instruments with different methods and sensors for acoustic measurements. Its results provide current sound levels over a very large region of the western South Atlantic, both in areas more and less affected by anthropogenic activities.

Does Covid-19 influence the dynamics of envenomation by animals in a country strongly affected by both conditions? Epidemiological data from Brazil - Pedro Ferreira Bisneto; Alexandre Vilhena da Silva Neto; Jady Shayenne Mota Cordeiro; Wuelton Marcelo Monteiro; Jacqueline de Almeida Gonçalves Sachett (Toxicon, 2024)

Seeing further into the early steps of the endangered atlantic goliath grouper (Epinephelus itajara): Eye lenses high resolution isotopic profiles reveal ontogenetic trophic and habitat shifts - Rodrigo F. Bastos; Mario V. Condini; Ester F. Barbosa; Rafael L. Oliveira; Lorena L. Almeida; Alexandre M. Garcia; Maurício Hostim-Silva (Marine Environmental Research, 2024)

Advancing air quality monitoring: A low-cost sensor network in motion – Part I - Carolina Correia; Pedro Santana; Vânia Martins; Pedro Mariano; Alexandre Almeida; Susana Marta Almeida (Journal of Environmental Management, 2024)

Carbon and nitrogen, humic and labile fractions in soil under clonal eucalyptus stands from cerrado - Wendel dos Santos Moraes; Luiz Fernandes Silva Dionisio; Gustavo Schwartz; Juliana Andrade Pereira; Jossimara Ferreira Damascena; Felipe Alexandre Rizzo; Alberto Bentes Brasil Neto; Camila de Almeida Milhomem; José Maria Arcanjo Alves; Renisson Neponuceno Araujo Filho; Renato de Almeida Sarmento; Alinne da Silva; et al. (European Journal of Forest Research, 2024)

Alternative system for micropropagation of Prunus campanulata (Maxim.) - Daniela Sanson; Alexandre Techy de Almeida Garrett; Isy Cavalhães Rodrigues; Gabriel de Magalhães Miranda; Fabricio William de Ávila; Cristiane Alves Fogaça; Ezequiel Gasparin; Rogério Bobrowski; Fabiana Schmidt Bandeira Peres (In Vitro Cellular & Developmental Biology - Plant, 2024)

Evaluation of Mastadenovirus and Rotavirus Presence in Phyllostomid, Vespertilionid, and Molossid Bats Captured in Rio Grande do Sul, Southern Brazil - Alexandre Sita; Gabriela Espíndola Birlem; Deivid de Souza da Silva; Gabriela Mattos Possamai; Karla Petry; Paula Rodrigues de Almeida; Larissa Mallmann; Janaína Franciele Stein; Meriane Demoliner; Juliana Schons Gularte; Alana Witt Hansen; André Alberto Witt; et al. (Food and Environmental Virology, 2024)

Evaluation of Extraction Methods to Detect Noroviruses in Ready-to-Eat Raw Milk Minas Artisanal Cheese - Carina Pacheco Cantelli; Marcio Roberto Silva; Laís Marques Pimenta; Guilherme Caetano Lanzieri Tavares; Gabriel Assad Baduy; André Almeida Santos Duch; Liliane Denize Miranda Menezes; Alexandre Madi Fialho; Adriana Gonçalves Maranhão; Tulio Machado Fumian; Marize Pereira Miagostovich; José Paulo Gagliardi Leite (Food and Environmental Virology, 2024)

Agroforestry can improve soil fertility and aggregate-associated carbon in highland soils in the Brazilian northeast - Rodrigo Santana Macedo; Letícia Moro; Cristiano dos Santos Sousa; Kalline de Almeida Alves Carneiro; Milton César Costa Campos; Alexandre Pereira de Bakker; Raphael Moreira Beirigo (Agroforestry Systems, 2024)

Toxicological assessment of photoactivated tetra-cationic porphyrin molecules under white light exposure in a Caenorhabditis elegans model - Gabriela Vitória de Oliveira; Marcell Valandro Soares; Larissa Marafiga Cordeiro; Aline Franzen da Silva; Luiza Venturini; Larissa Ilha; Fabiane Bicca Obetine Baptista; Tássia Limana da Silveira; Félix Alexandre Antunes Soares; Bernardo Almeida Iglesias (Toxicology, 2024)

Detection of pathogenic Leptospira spp. in unconventional pets - Bruna Carolina Ulsenheimer; Matheus Yuri dos Santos; Bruna Della Flora; Diego Andres Rodriguez Matarrita; Sônia de Avila Botton; Ana Eucares Von Laer; Daniela Isabel Brayer Pereira; Rafael Almeida Fighera; Alexandre Alberto Tonin (Comparative Immunology, Microbiology and Infectious Diseases, 2024)

Anaplasmosis outbreaks in taurine and zebu cattle in Brazil: causes, treatments, and Anaplasma marginale genetic diversity - Luccas Lourenzzo Lima Lins Leal; Alliny Souza de Assis Cavalcante; Igor Maciel Lopes de Moraes; Vanessa Salvador; Luiz Fellipe Monteiro Couto; Luciana Maffini Heller; Dina Maria Beltrán Zapa; Warley Vieira de Freitas Paula; Kamila Gaudêncio da Silva Sales; Eduardo Lima; Alexandre Braga Scarpa; Ricardo Antônio Amaral de Lemos; et al. (Tropical Animal Health and Production, 2024)

Camera trap surveys of A tlantic F orest mammals: A data set for analyses considering imperfect detection (2004–2020) - Ingridi Camboim Franceschi; Rubem Augusto da Paixão Dornas; Isabel Salgueiro Lermen; Artur Vicente Pfeifer Coelho; Ademir Henrique Vilas Boas; Adriano Garcia Chiarello; Adriano Pereira Paglia; Agnis Cristiane de Souza; Alana Rafaela Borsekowsky; Alessandro Rocha; Alex Bager; Alexander Zaidan de Souza; et al. (Ecology, 2024)
Camera traps became the main observational method of a myriad of species over large areas. Data sets from camera traps can be used to describe the patterns and monitor the occupancy, abundance, and richness of wildlife, essential information for conservation in times of rapid climate and land‐cover changes. Habitat loss and poaching are responsible for historical population losses of mammals in the Atlantic Forest biodiversity hotspot, especially for medium to large‐sized species. Here we present a data set from camera trap surveys of medium to large‐sized native mammals (>1 kg) across the Atlantic Forest. We compiled data from 5380 ground‐level camera trap deployments in 3046 locations, from 2004 to 2020, resulting in 43,068 records of 58 species. These data add to existing data sets of mammals in the Atlantic Forest by including dates of camera operation needed for analyses dealing with imperfect detection. We also included, when available, information on important predictors of detection, namely the camera brand and model, use of bait, and obstruction of camera viewshed that can be measured from example pictures at each camera location. Besides its application in studies on the patterns and mechanisms behind occupancy, relative abundance, richness, and detection, the data set presented here can be used to study species' daily activity patterns, activity levels, and spatiotemporal interactions between species. Moreover, data can be used combined with other data sources in the multiple and expanding uses of integrated population modeling. An R script is available to view summaries of the data set. We expect that this data set will be used to advance the knowledge of mammal assemblages and to inform evidence‐based solutions for the conservation of the Atlantic Forest. The data are not copyright restricted; please cite this paper when using the data.

Human health risks assessment of the fluctuations in mercury levels in seafood from different key regions of Rio de Janeiro, Brazil - Paloma de Almeida Rodrigues; Adriano Teixeira de Oliveira; Alexandre Mendes Ramos-Filho; Julia Vianna de Pinho; Gustavo Lata Neves; Carlos Adam Conte-Junior (Environmental Science and Pollution Research, 2024)

Artificial neural network modeling of the stability behavior of stainless steel I-beams with sinusoidal web openings - Adriano Silva de Carvalho; Alexandre Rossi; Marcela Moreira da Rocha Almeida; Yasin Onuralp Özkılıç; Carlos Humberto Martins (Engineering Structures, 2024)

Comparison of the performance of multiple imputation models in filling gaps in hourly and daily meteorological series from two locations in the state of São Paulo-Brazil - Luana Possari Maziero; Sérgio Augusto Rodrigues; Alexandre Dal Pai; Camila Pires Cremasco; Luís Roberto Almeida Gabriel Filho (Modeling Earth Systems and Environment, 2024)

Effects of GnRH analogs on strip spawning and steroid plasma levels of Colossoma macropomum - Rosilane Gomes Souza de Oliveira; Gabriela Brambila de Souza; Alexandre Nizio Maria; Ronãn Alves de Freitas; Fernanda Loureiro de Almeida (Aquaculture International, 2024)

Baseline metal and metalloid contamination in two marine sponge species, Hymeniacidon heliophila and Desmapsamma anchorata, from southeastern Brazil - Rachel Ann Hauser-Davis; Leandro Ribeiro dos Santos; João Victor Meirelles Leite; Regina Fonsêca de Almeida; Oswaldo Luiz de C. Maciel; Tatiana Dillenburg Saint Pierre; Bruno Correa Meurer; Oliver Alexandre F.C. Pereira (Marine Pollution Bulletin, 2024)

Long-term preservation of established fibroblast lines from six‐banded armadillos (Euphractus sexcintus, Linnaeus, 1758) by extended passage and cryopreservation - Denilsa Pires Fernandes; Érika Almeida Praxedes; João Vitor da Silva Viana; Maria Valéria de Oliveira Santos; Alexandre Rodrigues Silva; Carlos Iberê Alves Freitas; Alexsandra Fernandes Pereira (In Vitro Cellular & Developmental Biology - Animal, 2024)

Environmental vulnerability index in Dipteryx alata: influence of abiotic stresses on central processes of plant physiology and metabolism - Leticia Ferreira Sousa; Paulo Eduardo Menezes-Silva; Priscila Ferreira Batista; Ana Paula Silva Alves; Maria Clara de Andrade PereiraSilva; Sabrina Emanuella da Silva Almeida; Rauander Douglas Ferreira Barros Alves; Lucas Loram Lourenço; Layara Alexandre Bessa; Adinan Alves da Silva; Alan Carlos Costa; Anderson Rodrigo da Silva; et al. (Acta Physiologiae Plantarum, 2024)

Asynchronous contributions of decapod life history stages to the zooplankton of tropical estuarine, coastal and shelf ecosystems - new insights from semi-automatic image analysis - Denise Fabiana de Moraes Costa Schwamborn; Catarina R. Marcolin; Nathália Lins-Silva; Alexandre Oliveira de Almeida; Ralf Schwamborn (Journal of Marine Systems, 2024)

Somatic embryogenesis in Euterpe edulis Martius is improved by wounding, explant orientation, and suspension culture - Tamyris de Mello; Tatiane Dulcineia Silva; Tadeu Ériton Caliman Zanardo; Francine Alves Nogueira de Almeida; Luciano Bestete Oliveira; Clovis Eduardo Nunes Hegedus; Breno Benvindo dos Anjos; Edilson Romais Schmildt; Adésio Ferreira; Márcia Flores da Silva Ferreira; José Carlos Lopes; Glória Maria de Farias Viégas Aquije; et al. (Plant Cell, Tissue and Organ Culture (PCTOC), 2024)

New reports of Gilbertella persicaria causing post-harvest rot in different fruits in Brazil - Ana Elisa de Almeida Souza; André Luiz Cabral Monteiro de Azevedo Santiago; Amanda Cupertino de Queiroz Brito; Juliana Ferreira de Mello; José Vitorino da Silva Neto; Cristina Maria de Souza-Motta; Alexandre Reis Machado (Journal of Plant Diseases and Protection, 2024)

Recyclable liquid metal – Graphene supercapacitor - Afsaneh L. Sanati; Pedro Alhais Lopes; Alexandre Chambel; André F. Silva; Diogo M. Oliveira; Carmel Majidi; Anibal T. de Almeida; Mahmoud Tavakoli (Chemical Engineering Journal, 2024)

Paleosol marked by contrasting formation processes: A pilot study using digital morphometrics in Southeastern Brazil - Fernanda Almeida Bócoli; Sérgio Henrique Godinho Silva; Junior Cesar Avanzi; Bruno Montoani Silva; Vanêssa Lopes de Faria; Maria Cecília Vieira Totti; Alberto Vasconcellos Inda; Gustavo Frosi; Suane de Souza Franco Lima; Alexandre Uezu; Marco Aurélio Carbone Carneiro; Marta Vasconcelos Ottoni; et al. (CATENA, 2024)

Pathogenicity and symptomatology of Apoharknessia eucalyptorum on leaves and stems of Eucalyptus and Corymbia - Alexandre Techy de Almeida Garrett; Afonso Figueiredo Filho; Jafargholi Imani; Álvaro Figueredo dos Santos; Evandro Vagner Tambarussi; Mariane Bueno de Camargo; Flávio Augusto de Oliveira Garcia; Karl-Heinz Kogel (European Journal of Plant Pathology, 2024)

Do tides equally influence the reproductive cycle of two symbiotic estuarine shrimp? - Rodrigo Guéron; Douglas Fernandes Rodrigues Alves; Alexandre Oliveira Almeida (Regional Studies in Marine Science, 2023)

Fonsecaea pedrosoi produces ferricrocin and can utilize different host iron sources - Kassyo Lobato Potenciano da Silva; Dayane Moraes; Beatrix Lechner; Herbert Lindner; Hubertus Haas; Célia Maria Almeida Soares; Mirelle Garcia Silva-Bailão; Alexandre Melo Bailão (Fungal Biology, 2023)

High copper promotes cell wall remodeling and oxidative stress in Histoplasma capsulatum, as revealed by proteomics - Dayane Moraes; Leandro do Prado Assunção; Kassyo Lobato Potenciano da Silva; Célia Maria de Almeida Soares; Mirelle Garcia Silva-Bailão; Alexandre Melo Bailão (Fungal Biology, 2023)

Selective photoelectrocatalytic CO2 reduction to ethanol using nanotubular oxides grown on metastable Ti-Cu alloy - Juliana de Almeida; Stella Hoffman Câmara; Rodnei Bertazzoli; Krishnan Rajeshwar; Ricardo Alexandre Galdino da Silva; Christiane de Arruda Rodrigues (Chemical Engineering Journal, 2023)

Energetic responses of head-out water immersion at different temperatures during post-exercise recovery and its consequence on anaerobic mechanical power - Marcelo Coertjens; Patricia Chaves Coertjens; Marcus Peikriszwili Tartaruga; Tatiane Gorski; Adriano Eduardo Lima-Silva; Lorival José Carminatti; Paulo Otto Beyer; Ana Paula Viola de Almeida; Jeam Marcel Geremia; Leonardo Alexandre Peyré-Tartaruga; Luiz Fernando Martins Kruel (European Journal of Applied Physiology, 2023)

Methodological insights from unmanned system technologies in a rock quarry environment and geomining heritage site: coupling LiDAR-based mapping and GIS geovisualisation techniques - Ana Pires; André Dias; Pedro Silva; António Ferreira; Paulo Rodrigues; Tiago Santos; Alexandre Oliveira; Liliana Freitas; Alfredo Martins; José Almeida; Eduardo Silva; Helder I. Chaminé (Arabian Journal of Geosciences, 2023)

Stieleria tagensis sp. nov., a novel member of the phylum Planctomycetota isolated from Tagus River in Portugal - Ofélia Godinho; Dominika Klimek; Adrianna Jackiewicz; Bárbara Guedes; Eduarda Almeida; Rita Calisto; Inês Rosado Vitorino; José Diogo Neves Santos; Ignacio González; Alexandre Lobo-da-Cunha; Magdalena Calusinska; Sandra Quinteira; et al. (Antonie van Leeuwenhoek, 2023)
A bacterial strain was isolated from a brackish water sample of Tagus river, Alcochete, Portugal and was designated TO1_6 T . It forms light pink colonies on M13 medium supplemented with N -acetylglucosamine. Cells are pear-shaped to spherical, form rosettes and divide by budding. Strain TO1_6 T presents a mesophilic and neutrophilic profile, with optimum growth at 20 to 25 °C and pH 7.0 to 7.5, and vitamin supplementation is not required to promote its growth. The genome of the novel isolate is 7.77 Mbp in size and has a DNA G + C content of 56.3%. Based on its 16S rRNA gene sequence, this strain is affiliated with the phylum Planctomycetota . Further taxonomic characterization using additional phylogenetic markers, namely rpoB gene sequence (encoding the β-subunit of the DNA-dependent RNA polymerase), as well as Percentage of conserved proteins, average nucleotide identity and average amino acid identity, suggest the affiliation of strain TO1_6 T to the genus Stieleria , a recently described taxon in the family Pirellulaceae, order Pirellulales and class Planctomycetia . Based on the genotypic, phylogenetic and physiological characterization, we here describe a new species represented by the type strain TO1_6 T (= CECT 30432 T , = LMG 32465 T ), for which the name Stieleria tagensis sp. nov. is proposed.

Spray-chilling system in the initial cooling process of swine half carcasses - Alessandra Pereira dos Santos; Fabiana Ribeiro Caldara; Alexandre Rodrigo Mendes Fernandes; Maria Fernanda de Castro Burbarelli; Bruna de Souza Eberhart; Jean Kaique Valentim; Ibiara Correia de Lima Almeida Paz; Rodrigo Garófallo Garcia; Agnês Markiy Odakura (Meat Science, 2023)

Hydroclimatic influence on the trophic ecology of Atlantic goliath grouper juveniles (Epinephelus itajara) in a tropical estuary using non-lethal methodologies - Mario V. Condini; Alexandre M. Garcia; Rodrigo F. Bastos; Sabrina R. Vollrath; Ester F. Barbosa; Rafael L. Oliveira; Lorena L. Almeida; Maurício Hostim-Silva (Marine Environmental Research, 2023)

Giants of the Amazon: How does environmental variation drive the diversity patterns of large trees? - Robson Borges de Lima; Eric Bastos Görgens; Diego Armando S. da Silva; Cinthia Pereira de Oliveira; Anderson Pedro B. Batista; Rinaldo L. Caraciolo Ferreira; Flavia R. C. Costa; Renato A. Ferreira de Lima; Perseu da Silva Aparício; Jadson Coelho de Abreu; José Antônio Aleixo da Silva; Aretha Franklin Guimaraes; et al. (Global Change Biology, 2023)
For more than three decades, major efforts in sampling and analyzing tree diversity in South America have focused almost exclusively on trees with stems of at least 10 and 2.5 cm diameter, showing highest species diversity in the wetter western and northern Amazon forests. By contrast, little attention has been paid to patterns and drivers of diversity in the largest canopy and emergent trees, which is surprising given these have dominant ecological functions. Here, we use a machine learning approach to quantify the importance of environmental factors and apply it to generate spatial predictions of the species diversity of all trees (dbh ≥ 10 cm) and for very large trees (dbh ≥ 70 cm) using data from 243 forest plots (108,450 trees and 2832 species) distributed across different forest types and biogeographic regions of the Brazilian Amazon. The diversity of large trees and of all trees was significantly associated with three environmental factors, but in contrasting ways across regions and forest types. Environmental variables associated with disturbances, for example, the lightning flash rate and wind speed, as well as the fraction of photosynthetically active radiation, tend to govern the diversity of large trees. Upland rainforests in the Guiana Shield and Roraima regions had a high diversity of large trees. By contrast, variables associated with resources tend to govern tree diversity in general. Places such as the province of Imeri and the northern portion of the province of Madeira stand out for their high diversity of species in general. Climatic and topographic stability and functional adaptation mechanisms promote ideal conditions for species diversity. Finally, we mapped general patterns of tree species diversity in the Brazilian Amazon, which differ substantially depending on size class.

Protein profiles identified by LC-MS/MS demonstrate change in beta oxidation, ketogenesis, and propionate metabolism in rumen epithelium with different additives - Leone Campos Rocha; Andrey Sávio de Almeida Assunção; Renata Aparecida Martins; Victor Valério de Carvalho; Alexandre Perdigão; Marília Afonso Rabelo Buzalaf; Jiri Adamec; Camila Pereira Braga; Danilo Domingues Millen; José Cavalcante Souza Vieira; Pedro de Magalhães Padilha (Livestock Science, 2023)

From waste to the gut: Can blackcurrant press cake be a new functional ingredient? Insights on in vivo microbiota modulation, oxidative stress, and inflammation - Amanda dos Santos Lima; Rômulo Dias Novaes; Lucas Cezar Pinheiro; Leonardo Augusto de Almeida; Hercia Stampini Duarte Martino; Alexandre Giusti-Paiva; Nora Pap; Daniel Granato; Luciana Azevedo (Food Research International, 2023)

Phylogenomic evolutionary insights in the fern family Gleicheniaceae - Lucas Vieira Lima; Alexandre Salino; Michael Kessler; Germinal Rouhan; Weston L. Testo; Caio Suzart Argolo; GoFlag Consortium; Thaís Elias Almeida (Molecular Phylogenetics and Evolution, 2023)

Vaginal temperature modeling in Holstein cows and cluster analysis by the cophenetic correlation coefficient - Marcos Vinícius da Silva; Héliton Pandorfi; Maria Simone Mendes Peixoto; José Antonio Delfino Barbosa Filho; Gledson Luiz Pontes de Almeida; Iran José Oliveira da Silva; Kenio Patrício Lima de Oliveira; Vinícius de Sena Sales Viana; José Francisco de Oliveira-Júnior; Cristiane Guiselini; Gabriel Thales Barboza Marinho; Marcio Mesquita; et al. (Journal of Thermal Biology, 2023)

Metarhizium anisopliae E6 secretome reveals molecular players in host specificity and toxicity linked to cattle tick infection - Laura Rascovetzki Saciloto-de-Oliveira; Leonardo Broetto; Camila Innocente Alves; Rafael Lopes da Rosa; Yohana Porto Calegari Alves; Rodrigo Campos da Silva; Markus Berger; Alexandre José Macedo; Pedro Ferrari Dalberto; Cristiano Valim Bizarro; Jorge Almeida Guimarães; John R. Yates; et al. (Fungal Biology, 2023)

The decline of the ecosystem services generated by anadromous fish in the Iberian Peninsula - Pedro R. Almeida; Catarina S. Mateus; Carlos M. Alexandre; Sílvia Pedro; Joana Boavida-Portugal; Ana F. Belo; Esmeralda Pereira; Sara Silva; Inês Oliveira; Bernardo R. Quintella (Hydrobiologia, 2023)
This work aims to present an historical review of the ecosystem services provided by anadromous fish (i.e., species that migrate from the sea to the river to spawn) throughout Human time, as well as of the main related threats, focusing on the Iberian Peninsula region. Anadromous fish provide important provision, cultural, regulatory and supporting ecosystem services across their distribution range and have been extensively exploited by humans since prehistoric times. In the Iberian Peninsula, sea lamprey, allis and twaite shads, sea trout, Atlantic salmon and European sturgeon were once abundantly present in several river basins covering what is now Portuguese and Spanish territory. These species have suffered a severe decline across their distribution range, mainly due to habitat loss and overexploitation. Considered regal delicacies, these fishes were once a statement on the tables of the highest social classes, a much appreciated bounty for the poorer population and are still an important part of the local gastronomy and economy. Such high economic and cultural interest encouraged intensive fishing. Currently, management efforts are being implemented, pairing habitat rehabilitation (e.g., construction of fish passes in obstacles to migration such as weirs and dams) with sustainable fisheries. Considering the present climate change scenario, these species are bound to endure increased pressures, demanding novel management approaches to ensure population numbers that are able to secure their sustainable exploitation.

Mercury contamination in seafood from an aquatic environment impacted by anthropic activity: seasonality and human health risk - Paloma de Almeida Rodrigues; Júlia Vianna de Pinho; Alexandre Mendes Ramos-Filho; Gustavo Lata Neves; Carlos Adam Conte-Junior (Environmental Science and Pollution Research, 2023)

Copper acquisition and detoxification machineries are conserved in dimorphic fungi - Dayane Moraes; Jackeliny Garcia Costa Rodrigues; Marielle Garcia Silva; Lucas Weba Soares; Célia Maria de Almeida Soares; Alexandre Melo Bailão; Mirelle Garcia Silva-Bailão (Fungal Biology Reviews, 2023)

Identification of Clinical Trichosporon asteroides Strains by MALDI-TOF Mass Spectrometry: Evaluation of the Bruker Daltonics Commercial System and an In-House Developed Library - Elaine Cristina Francisco; Mexx Ebbing; Arnaldo Lopes Colombo; Ferry Hagen; Guilherme M. Chaves; Ana Verena A. Mendes; Marcio de Oliveira Silva; Maria Goreth de Andrade Barberino; Rejane Pereira Neves; Monica Borges Botura; Rosane C. Hahn; João Nóbrega de Almeida Junior; et al. (Mycopathologia, 2023)

Richness of Nigrospora spp. (Apiosporaceae) in Manihot esculenta in Brazil and the description of three new species - Amanda Cupertino de Queiroz Brito; Juliana Ferreira de Mello; Ana Elisa de Almeida Souza; Sandy dos Santos Nascimento; Cristina Maria de Souza-Motta; Alexandre Reis Machado (Mycological Progress, 2023)

Modeling and optimization of the pyrolysis oil production process from polypropylene for the production of aviation kerosene - Heraclito Alexandre dos Santos; Igor José Boggione Santos; Cristiane Medina Finzi Quintão; Vagner Fernandes Knupp; Renata Carolina Zanetti Lofrano; Eliane Cristina de Oliveira; Gisella Lamas Samanamud; Mateus de Souza Amaral; Alexandre Boscaro França; Mariana Arruda Pereira; Matheus Teixeira Araújo Silva; Carla Cristina Almeida Loures; et al. (Clean Technologies and Environmental Policy, 2023)

Spatial non-stationarity in the distribution of fish species richness of tropical streams - Thiago Bernardi Vieira; Jorge Iván Sánchez-Botero; Danielle Sequeira Garcez; Sergio Maia Queiroz Lima; Carla Simone Pavanelli; Lilian Casatti; Welber Senteio Smith; Evanilde Benedito; Rosana Mazzoni; Paulo Santos Pompeu; Carlos Sérgio Agostinho; Luciano Fogaça de Assis Montag; et al. (Community Ecology, 2023)

NEOTROPICAL FRESHWATER FISHES : A dataset of occurrence and abundance of freshwater fishes in the Neotropics - Lívia Helena Tonella; Renata Ruaro; Vanessa Salete Daga; Diego Azevedo Zoccal Garcia; Oscar Barroso Vitorino; Tatiana Lobato‐de Magalhães; Roberto Esser dos Reis; Fabio Di Dario; Ana Cristina Petry; Michael Maia Mincarone; Luciano Fogaça de Assis Montag; Paulo Santos Pompeu; et al. (Ecology, 2023)
The Neotropical region hosts 4225 freshwater fish species, ranking first among the world's most diverse regions for freshwater fishes. Our NEOTROPICAL FRESHWATER FISHES data set is the first to produce a large‐scale Neotropical freshwater fish inventory, covering the entire Neotropical region from Mexico and the Caribbean in the north to the southern limits in Argentina, Paraguay, Chile, and Uruguay. We compiled 185,787 distribution records, with unique georeferenced coordinates, for the 4225 species, represented by occurrence and abundance data. The number of species for the most numerous orders are as follows: Characiformes (1289), Siluriformes (1384), Cichliformes (354), Cyprinodontiformes (245), and Gymnotiformes (135). The most recorded species was the characid Astyanax fasciatus (4696 records). We registered 116,802 distribution records for native species, compared to 1802 distribution records for nonnative species. The main aim of the NEOTROPICAL FRESHWATER FISHES data set was to make these occurrence and abundance data accessible for international researchers to develop ecological and macroecological studies, from local to regional scales, with focal fish species, families, or orders. We anticipate that the NEOTROPICAL FRESHWATER FISHES data set will be valuable for studies on a wide range of ecological processes, such as trophic cascades, fishery pressure, the effects of habitat loss and fragmentation, and the impacts of species invasion and climate change. There are no copyright restrictions on the data, and please cite this data paper when using the data in publications.

Water content as a deterministic factor in the assessment of cohesive character in soils of Coastal Tablelands (Northeast, Brazil) - Alexandre dos Santos Queiroz; Carlos Tadeu dos Santos Dias; Angélica da Silva Lopes; Ícaro Vasconcelos do Nascimento; Lucas de Sousa Oliveira; Brivaldo Gomes de Almeida; José Coelho de Araújo Filho; Luciano da Silva Souza; Marlen Barros e Silva; Ricardo Espíndola Romero; Raul Shiso Toma; Helon Hébano de Freitas Sousa; et al. (Geoderma Regional, 2023)

Inoculation with Azospirillum brasilense as a strategy to enhance sugarcane biomass production and bioenergy potential - Daniele Scudeletti; Carlos Alexandre Costa Crusciol; Letusa Momesso; João William Bossolani; Luiz Gustavo Moretti; Elisa Fidêncio De Oliveira; Brenda Servaz Tubaña; Marcelo de Almeida Silva; Sérgio Gustavo Quassi de Castro; Mariangela Hungria (European Journal of Agronomy, 2023)

Antimicrobial peptides against polymyxin-resistant Klebsiella pneumoniae: a patent review - Gleyce Hellen de Almeida de Souza; Luana Rossato; Alexandre Ribeiro de Oliveira; Simone Simionatto (World Journal of Microbiology and Biotechnology, 2023)

Bacterial identification in cerebrospinal fluid of domestic species with neurologic signs: a retrospective case-series study in 136 animals (2005–2021) - Márcio Garcia Ribeiro; Thiago Tourinho Pereira; Patrik Júnior de Lima Paz; Beatriz Oliveira de Almeida; Carmen S. Araújo Cerviño; Carolina Aparecida Rodrigues; Gabrielly Terra Sartori Santos; Larissa Maria de Souza Freire; Fábio Vinicius Ramos Portilho; Marcelo Fagali Árabe Filho; Natália Rodrigues Paschoal; Thaís Spessotto Bello; et al. (Brazilian Journal of Microbiology, 2023)

Tolerance in rice genotypes to the sugarcane borer Diatraea saccharalis (Lepidoptera: Crambidae) - Ana Paula Pelosi; Franciele Cristina da Silva; Adriana G. Vaz; André Cirilo de S. Almeida; Anderson Rodrigo da Silva; Flávio G. de Jesus; José Alexandre de F. Barrigossi (Biologia, 2023)

Tissue-resident glial cells associate with tumoral vasculature and promote cancer progression - Beatriz G. S. Rocha; Caroline C. Picoli; Bryan O. P. Gonçalves; Walison N. Silva; Alinne C. Costa; Michele M. Moraes; Pedro A. C. Costa; Gabryella S. P. Santos; Milla R. Almeida; Luciana M. Silva; Youvika Singh; Marcelo Falchetti; et al. (Angiogenesis, 2023)

Egg production by the exotic shrimp Athanas dimorphus (Caridea: Alpheidae) in a harbor area in northeastern Brazil - Renata Fernanda Lima-Silva; Guidomar Oliveira Soledade; Régis Augusto Pescinelli; Alexandre Oliveira Almeida (Regional Studies in Marine Science, 2023)

Geographic patterns of tree dispersal modes in Amazonia and their ecological correlates - Diego F. Correa; Pablo R. Stevenson; Maria Natalia Umaña; Luiz de Souza Coelho; Diógenes de Andrade Lima Filho; Rafael P. Salomão; Iêda Leão do Amaral; Florian Wittmann; Francisca Dionízia de Almeida Matos; Carolina V. Castilho; Oliver L. Phillips; Juan Ernesto Guevara; et al. (Global Ecology and Biogeography, 2023)
Aim To investigate the geographic patterns and ecological correlates in the geographic distribution of the most common tree dispersal modes in Amazonia (endozoochory, synzoochory, anemochory and hydrochory). We examined if the proportional abundance of these dispersal modes could be explained by the availability of dispersal agents (disperser‐availability hypothesis) and/or the availability of resources for constructing zoochorous fruits (resource‐availability hypothesis). Time period Tree‐inventory plots established between 1934 and 2019. Major taxa studied Trees with a diameter at breast height (DBH) ≥ 9.55 cm. Location Amazonia, here defined as the lowland rain forests of the Amazon River basin and the Guiana Shield. Methods We assigned dispersal modes to a total of 5433 species and morphospecies within 1877 tree‐inventory plots across terra‐firme, seasonally flooded, and permanently flooded forests. We investigated geographic patterns in the proportional abundance of dispersal modes. We performed an abundance‐weighted mean pairwise distance (MPD) test and fit generalized linear models (GLMs) to explain the geographic distribution of dispersal modes. Results Anemochory was significantly, positively associated with mean annual wind speed, and hydrochory was significantly higher in flooded forests. Dispersal modes did not consistently show significant associations with the availability of resources for constructing zoochorous fruits. A lower dissimilarity in dispersal modes, resulting from a higher dominance of endozoochory, occurred in terra‐firme forests (excluding podzols) compared to flooded forests. Main conclusions The disperser‐availability hypothesis was well supported for abiotic dispersal modes (anemochory and hydrochory). The availability of resources for constructing zoochorous fruits seems an unlikely explanation for the distribution of dispersal modes in Amazonia. The association between frugivores and the proportional abundance of zoochory requires further research, as tree recruitment not only depends on dispersal vectors but also on conditions that favour or limit seedling recruitment across forest types.

Physicochemical characteristics and antimicrobial activity of Origanum vulgare L. essential oil and carvacrol on cariogenic bacteria: an in vitro and in silico study - Ellen Caroline Araújo da Silva; Letícia Lopes Leuthier; Alexandre Almeida Júnior; Jocianelle Maria Felix Fernandes Nunes; Fábio Correia Sampaio; Isabela Albuquerque Passos Farias (Natural Product Research, 2022)

Detection of human Mastadenovirus C in wild guinea pigs (Cavia aperea aperea) feces - Alexandre Sita; Gabriela E. Birlem; Paula R. de Almeida; Janaína F. Stein; Larissa Mallmann; Meriane Demoliner; Mariana S. da Silva; Juliana S. Gularte; Alana W. Hansen; Juliane D. Fleck; Fernando R. Spilki; Severino S. S. Higino; et al. (Brazilian Journal of Microbiology, 2022)

Microbial bioremediation of pesticides in agricultural soils: an integrative review on natural attenuation, bioaugmentation and biostimulation - Paulo Renato Matos Lopes; Victor Hugo Cruz; Alexandre Barretto de Menezes; Biana Pelissari Gadanhoto; Bruno Rafael de Almeida Moreira; Carolina Rosai Mendes; Dânia Elisa Christofoletti Mazzeo; Guilherme Dilarri; Renato Nallin Montagnolli (Reviews in Environmental Science and Bio/Technology, 2022)

Silicon amendment induces resistance in rice to Diatraea saccharalis (Lepidoptera: Crambidae) - Ana Paula Pelosi; Franciele Cristina da Silva; Adriana G. Vaz; André Cirilo S. Almeida; Anderson Rodrigo da Silva; Michael J. Stout; Flávio G. de Jesus; José Alexandre F. Barrigossi (Arthropod-Plant Interactions, 2022)

Taxonomic and functional diversity patterns of stream fish assemblages from Brazilian Atlantic Rain Forest - Mauricio Cetra; Lucas Alejandro Garibaldi; Fabrício Barreto Teresa; Alexandre Peressin; Bruna Botti Cruz; Bruno José Gomes de Mello; Fernanda Ayumi Teshima; Rodrigo da Silva Almeida (Fisheries Management and Ecology, 2022)
Disentangling the hierarchical structure of river systems and multi‐scale environmental effects is essential for understanding freshwater fish community structure and function. We sampled 70 stream stretches to investigate how the taxonomic and functional composition and diversity of fish assemblages responded to the environment considering a hierarchical organisation of streams in three Brazilian watersheds (Upper Sorocaba, Upper Paranapanema and Upper Ribeira de Iguape). Functional diversity indicated that stream fish community function was independent of the watershed. The most critical environmental variable was substrate gradient. In streams with a consolidated substrate, equitability and functional dispersion were low due to invertivores occurring in this type of substrate. Our results highlight the importance of local environmental filters for shaping streams fish assemblages across different basins. This shaping was more evident when functional descriptors of assemblages were analysed, thereby reinforcing the importance of an approach based on traits as a tool to elucidate local community assembly processes at broader spatial scales.

Correction to: SARS-CoV-2 removal with a polyurethane foam composite - Guilherme Pereira Schoeler; Thays França Afonso; Carolina Faccio Demarco; Victor dos Santos Barboza; Tito Roberto Sant’anna Cadaval; Andrei Valerão Igansi; Marcos Alexandre Gelesky; Janice Luehring Giongo; Rodrigo de Almeida Vaucher; Rafael de Avila Delucis; Robson Andreazza (Environmental Science and Pollution Research, 2022)

Essential oil and residual distillation water of Pterocaulon polystachyum DC: composition, antifungal activity, and mathematical modeling of steam distillation - Júlia M. Scopel; Bruna Medeiros-Neves; Helder Teixeira; Sérgio A.L Bordignon; Alexandre M. Fuentefria; Gabriella da Rosa Monte Machado; Rafael N. Almeida; Eduardo Cassel; Gilsane L. von Poser; Rubem M. F. Vargas (Plant Biosystems, 2022)

SARS-CoV-2 removal with a polyurethane foam composite - Guilherme Pereira Schoeler; Thays França Afonso; Carolina Faccio Demarco; Victor dos Santos Barboza; Tito Roberto Sant’anna Cadaval; Andrei Valerão Igansi; Marcos Alexandre Gelesky; Janice Luehring Giongo; Rodrigo de Almeida Vaucher; Rafael de Avila Delucis; Robson Andreazza (Environmental Science and Pollution Research, 2022)

Macro-Habitat Suitability for Threespine Stickleback (Gasterosteus aculeatus L.) Near the Southern Limit of Its Global Distribution: Implications for Species Management and Conservation - Andre Moreira; Joana Boavida-Portugal; Pedro R. Almeida; Sara Silva; Carlos M. Alexandre (Fishes, 2022)
The threespine stickleback is a freshwater fish listed as endangered in Portugal, near the southern limit of the species global distribution. However, few measures have been proposed aiming at the conservation of this species in suboptimal environments. From existing databases and specific sampling campaigns, we obtained occurrence data of threespine stickleback for a total of 646 sites. The occurrence data, together with 15 environmental macrohabitat predictors, were used to model the potential distribution of the species using an ensemble of species distribution models. Through the results of our final ensemble, we project that the threespine stickleback occurs predominantly at lower stretches of river systems, where sandy substrate is dominant and flow is higher. Within this region, sticklebacks are also more likely to occur in sites with high levels of rainfall in the driest month, thus avoiding locations with high potential for drying during summer. The species also tends to avoid steep slope areas with high levels of annual precipitation. Based on our results, a map of the species probability of occurrence was generated and river sections were categorized into levels according to their importance for the species’ conservation.

Does the same refuge signify the same reproductive tactics? Comparing the mating systems of two symbiont alpheid shrimps (Crustacea: Decapoda) - Rodrigo Guéron; Douglas Fernandes Rodrigues Alves; José Roberto Botelho de Souza; Alexandre Oliveira Almeida (Marine Ecology, 2022)
Animal populations can present different mating tactics according to the number of mates males or females obtain. The limiting factors for copulation in symbiont crustaceans are the size, structural complexity, and density of refuge, in addition to predation risk outside their shelters. In this study, we aimed to investigate, comparatively, if the occupation of the same refuge leads to the same reproductive tactic in two symbiont species of alpheid shrimps. For this purpose, we described the population distribution of Alpheus estuariensis , a burrowing shrimp, and Salmoneus carvachoi , a tenant species, in an intertidal mudflat in Pernambuco, northeastern Brazil. Alpheus estuariensis experiences sexual dimorphism relative to body and cheliped size, where males present larger body sizes and allocate more resources to cheliped growth than females. However, both males and females presented positive allometric growth in chelipeds. In S. carvachoi , male‐phase individuals reach smaller body sizes than hermaphrodites. Male‐phase shrimps experience positive allometry in cheliped size, while hermaphrodites do not. Both species were found inhabiting burrows as sexual pairs more frequently than expected by chance. Paired females of A. estuariensis were found carrying embryos more frequently than solitary ones. We did not find a statistical difference between the frequency of single and paired ovigerous hermaphrodites in S. carvachoi . Our results indicate that A. estuariensis is social monogamous, while S. carvachoi is promiscuous. We argue that different biological and ecological aspects of these species could explain the distinct tactics adopted by them. Alpheus estuariensis digs its own refuge and is a much larger species, bearing a more robust cheliped than S. carvachoi . Thus, we argue that the burrowing species ( A. estuariensis ) should monopolize and defend their refuge, and S. carvachoi only takes advantage of this resource.

Long‐term unsustainable patterns of development rather than recent deforestation caused the emergence of Orthocoronavirinae species - Sérvio P. Ribeiro; Debmalya Barh; Bruno Silva Andrade; Raner José Santana Silva; Diogo Henrique Costa‐Rezende; Paula Luize Camargos Fonseca; Sandeep Tiwari; Marta Giovanetti; Luiz Carlos Junior Alcantara; Vasco Ariston Azevedo; Preetam Ghosh; José Alexandre F. Diniz‐Filho; et al. (Environmental Microbiology, 2022)
We investigated whether a set of phylogeographical tracked emergent events of Orthocoronavirinae were related to developed, urban and polluted environments worldwide. We explored coronavirus records in response to climate (rainfall parameters), population density, CO 2 emission, Human Developmental Index (HDI) and deforestation. We contrasted environmental characteristics from regions with spillovers or encounters of wild Orthocoronavirinae against adjacent areas having best‐preserved conditions. We used all complete sequenced CoVs genomes deposited in NCBI and GISAID databases until January 2021. Except for Deltacoronavirus, concentrated in Hong Kong and in birds, the other three genera were scattered all over the planet, beyond the original distribution of the subfamily, and found in humans, mammals, fishes and birds, wild or domestic. Spillovers and presence in wild animals were only reported in developed/densely populated places. We found significantly more occurrences reported in places with higher HDI, CO 2 emission, or population density, along with more rainfall and more accentuated seasonality. Orthocoronavirinae occurred in areas with significantly higher human populations, CO 2 emissions and deforestation rates than in adjacent locations. Intermediately disturbed ecosystems seemed more vulnerable for Orthocoronavirinae emergence than forested regions in frontiers of deforestation. Sadly, people experiencing poverty in an intensely consumerist society are the most vulnerable.

Widespread Hybridization between Invasive Bleak (Alburnus alburnus) and Iberian Chub (Squalius spp.): A Neglected Conservation Threat - Manuel Curto; Miguel Morgado-Santos; Carlos M. Alexandre; Maria Judite Alves; Hugo F. Gante; Christos Gkenas; João P. Medeiros; Paulo J. Pinheiro; Pedro R. Almeida; Maria Filomena Magalhães; Filipe Ribeiro (Fishes, 2022)
Hybridization between native and nonnative fish species is a major conservation issue, especially in ecosystems with high levels of endemism, such as Iberian streams. To date, hybridization with the invasive bleak Alburnus alburnus has been reported for the Iberian chub Squalius alburnoides and S. pyrenaicus and in scattered locations only. However, the bleak is spreading in the region, potentially increasing the risks of hybridization with other Squalius species. To gather a more comprehensive picture on the current geography of hybridization, we compiled records on hybrids between bleak and chub in Portugal and conducted genetical assessments of hybrids between bleak and S. carolitertii. We found that hybridization with bleak is widespread throughout Portuguese river basins and involves at least S. alburnoides, S. pyrenaicus and S. carolitertii. Hybridization with bleak may not only cause waste of reproductive effort and damage the genetic integrity of these endemic species but also promote shifts in the reproductive dynamics of the S. alburnoides hybrid complex, which includes individuals with various ploidy levels and combinations of parental genomes, reproducing sexually and asexually. We recommend that future studies characterize the fitness of bleak hybrids and their ecological and genetic interactions with native fish, in order to design effective conservation measures.

AMAZONIA CAMTRAP: A data set of mammal, bird, and reptile species recorded with camera traps in the Amazon forest - Ana Carolina Antunes; Anelise Montanarin; Diogo Maia Gräbin; Erison Carlos dos Santos Monteiro; Fernando Ferreira de Pinho; Guilherme Costa Alvarenga; Jorge Ahumada; Robert B. Wallace; Emiliano Esterci Ramalho; Adrian Paul Ashton Barnett; Alex Bager; Alexandre Martins Costa Lopes; et al. (Ecology, 2022)
The Amazon forest has the highest biodiversity on Earth. However, information on Amazonian vertebrate diversity is still deficient and scattered across the published, peer‐reviewed, and gray literature and in unpublished raw data. Camera traps are an effective non‐invasive method of surveying vertebrates, applicable to different scales of time and space. In this study, we organized and standardized camera trap records from different Amazon regions to compile the most extensive data set of inventories of mammal, bird, and reptile species ever assembled for the area. The complete data set comprises 154,123 records of 317 species (185 birds, 119 mammals, and 13 reptiles) gathered from surveys from the Amazonian portion of eight countries (Brazil, Bolivia, Colombia, Ecuador, French Guiana, Peru, Suriname, and Venezuela). The most frequently recorded species per taxa were: mammals: Cuniculus paca (11,907 records); birds: Pauxi tuberosa (3713 records); and reptiles: Tupinambis teguixin (716 records). The information detailed in this data paper opens up opportunities for new ecological studies at different spatial and temporal scales, allowing for a more accurate evaluation of the effects of habitat loss, fragmentation, climate change, and other human‐mediated defaunation processes in one of the most important and threatened tropical environments in the world. The data set is not copyright restricted; please cite this data paper when using its data in publications and we also request that researchers and educators inform us of how they are using these data.

Sorbitan Monolaurate–Containing Liposomes Enhance Skin Cancer Cell Cytotoxicity and in Association with Microneedling Increase the Skin Penetration of 5-Fluorouracil - Luiziana Cavalcante Costa Fernandes Crisóstomo; Genuína Stephanie Guimarães Carvalho; Luzia Kalyne Almeida Moreira Leal; Tamara Gonçalves de Araújo; Karina Alexandre Barros Nogueira; Durcilene Alves da Silva; Fábio de Oliveira Silva Ribeiro; Raquel Petrilli; Josimar O. Eloy (AAPS PharmSciTech, 2022)

MAMMALS IN PORTUGAL : A data set of terrestrial, volant, and marine mammal occurrences in P ortugal - Clara Grilo; Beatriz C. Afonso; Filipe Afonso; Marta Alexandre; Sara Aliácar; Ana Almeida; Ivan Prego Alonso; Francisco Álvares; Paulo Alves; Paulo Célio Alves; Pedro Alves; Anabela Amado; et al. (Ecology, 2022)
Mammals are threatened worldwide, with ~26% of all species being included in the IUCN threatened categories. This overall pattern is primarily associated with habitat loss or degradation, and human persecution for terrestrial mammals, and pollution, open net fishing, climate change, and prey depletion for marine mammals. Mammals play a key role in maintaining ecosystems functionality and resilience, and therefore information on their distribution is crucial to delineate and support conservation actions. MAMMALS IN PORTUGAL is a publicly available data set compiling unpublished georeferenced occurrence records of 92 terrestrial, volant, and marine mammals in mainland Portugal and archipelagos of the Azores and Madeira that includes 105,026 data entries between 1873 and 2021 (72% of the data occurring in 2000 and 2021). The methods used to collect the data were: live observations/captures (43%), sign surveys (35%), camera trapping (16%), bioacoustics surveys (4%) and radiotracking, and inquiries that represent less than 1% of the records. The data set includes 13 types of records: (1) burrows | soil mounds | tunnel, (2) capture, (3) colony, (4) dead animal | hair | skulls | jaws, (5) genetic confirmation, (6) inquiries, (7) observation of live animal (8), observation in shelters, (9) photo trapping | video, (10) predators diet | pellets | pine cones/nuts, (11) scat | track | ditch, (12) telemetry and (13) vocalization | echolocation. The spatial uncertainty of most records ranges between 0 and 100 m (76%). Rodentia ( n =31,573) has the highest number of records followed by Chiroptera ( n = 18,857), Carnivora ( n = 18,594), Lagomorpha ( n = 17,496), Cetartiodactyla ( n = 11,568) and Eulipotyphla ( n = 7008). The data set includes records of species classified by the IUCN as threatened (e.g., Oryctolagus cuniculus [ n = 12,159], Monachus monachus [ n = 1,512], and Lynx pardinus [ n = 197]). We believe that this data set may stimulate the publication of other European countries data sets that would certainly contribute to ecology and conservation‐related research, and therefore assisting on the development of more accurate and tailored conservation management strategies for each species. There are no copyright restrictions; please cite this data paper when the data are used in publications.

Ventrolateral periaqueductal gray matter integrative system of defense and antinociception - Gustavo Henrique de Mello Rosa; Farhad Ullah; Yara Bezerra de Paiva; Juliana Almeida da Silva; Luiz Guilherme S. Branco; Alexandre Pinto Corrado; Priscila Medeiros; Norberto Cysne Coimbra; Audrey Franceschi Biagioni (Pflügers Archiv - European Journal of Physiology, 2022)
Defensive responses are neurophysiological processes crucial for survival during threatening situations. Defensive immobility is a common adaptive response, in rodents, elaborated by ventrolateral periaqueductal gray matter (vlPAG) when threat is unavoidable. It is associated with somatosensory and autonomic reactions such as alteration in the sensation of pain and rate of respiration. In this study, defensive immobility was assessed by chemical stimulation of vlPAG with different doses of NMDA (0.1, 0.3, and 0.6 nmol). After elicitation of defensive immobility, antinociceptive and respiratory response tests were also performed. Results revealed that defensive immobility was followed by a decrease in the nociceptive perception. Furthermore, the lowest dose of NMDA induced antinociceptive response without eliciting defensive immobility. During defensive immobility, respiratory responses were also disturbed. Interestingly, respiratory rate was increased and interspersed with prolonged expiratory phase of breathing. These findings suggest that vlPAG integrates three different defensive behavioral responses, contributing to the most effective defensive strategies during threatening situations.

The sexual reproduction of the nontarget planarian Girardia tigrina is affected by ecologically relevant concentrations of difenoconazole: new sensitive tools in ecotoxicology - Aline Silvestre Pereira Dornelas; Joel Santiago de Jesus Ferreira; Laila Cristina Rezende Silva; Althiéris de Souza Saraiva; Grasiele Soares Cavallini; Carlos Alexandre Sarabando Gravato; Amadeu Mortágua Velho da Maia Soares; Renato Almeida Sarmento (Environmental Science and Pollution Research, 2022)

SIA‐BRA: A database of animal stable carbon and nitrogen isotope ratios of Brazil - Thaís Rovere Diniz‐Reis; Fernanda Gaudio Augusto; Adibe Luiz Abdalla Filho; Maria Gabriella da Silva Araújo; Siglea Sanna Freitas Chaves; Rodrigo Figueiredo Almeida; Elen Blanco Perez; Carla da Penha Simon; Janaína Leite de Souza; Cristiane Formigosa Gadelha da Costa; Taciana Figueiredo Gomes; Melissa Gaste Martinez; et al. (Global Ecology and Biogeography, 2022)
Motivation SIA‐BRA is a data set that compiles stable carbon (C) and nitrogen (N) isotope ratios of terrestrial and aquatic animals sampled in Brazilian biomes and coastal marine areas. Stable isotope ratios are helpful in animal ecology for several reasons; for instance, they can be used to investigate trophic niches, energy sources (diet tracing) and to track migration patterns. The Neotropics are considered one of the most undersampled regions of the world. Given that Brazil is a continental country where most of the dietary ecology of animal species is under‐assessed, we believe that the SIA‐BRA can provide important complementary information to address this gap in the literature. Additionally, the SIA‐BRA data set allows future investigations to address many questions concerning diet tracing, habitat use, food webs, foraging ecology, physiological aspects and effects of phylogeny on dietary ecology. Main type of variable investigated Carbon and nitrogen stable isotope ratios for terrestrial and aquatic animals. Spatial location and grain The SIA‐BRA included animal tissues sampled in 964 sites in the main Brazilian biomes and coastal marine areas. Time period The data represent information published and/or sampled from 1984 to 2021. Major taxa studied and measurement level The SIA‐BRA contains isotopic data of c . 21,804 non‐captive wildlife specimens, excluding livestock production or laboratory experiments. They were 13,881 vertebrates and 7,923 invertebrates. They were divided into the following habitats: terrestrial (30% of the total), freshwater (27%), oceanic (40%) and estuarine (4%). There were 11 phyla, with a clear dominance of Chordata (64%) and Arthropoda (29%), 36 classes, 154 orders, 473 families, 894 genera and 1,157 species. Software format Data are supplied as a comma‐delimited text file (.csv).

Effect of acute swimming exercise at different intensities but equal total load over metabolic and molecular responses in swimming rats - Lucas Dantas Maia Forte; Natália de Almeida Rodrigues; André Vitor Cordeiro; Thais de Fante; Laís Angélica de Paula Simino; Adriana de Souza Torsoni; Márcio Alberto Torsoni; Claudio Alexandre Gobatto; Fúlvia Barros Manchado-Gobatto (Journal of Muscle Research and Cell Motility, 2022)

Advances in Brazil Nut Tree Ecophysiology: Linking Abiotic Factors to Tree Growth and Fruit Production - Karen Cristina Pires da Costa; José Francisco de Carvalho Gonçalves; Alexandre Leão Gonçalves; Adamir da Rocha Nina Junior; Roberto Kirmayr Jaquetti; Vinícius Fernandes de Souza; Josiane Celerino de Carvalho; Andreia Varmes Fernandes; Joelma Keith Rodrigues; Gleisson de Oliveira Nascimento; Lúcia Helena de O. Wadt; Karen A. Kainer; et al. (Current Forestry Reports, 2022)

ATLANTIC ANTS: a data set of ants in Atlantic Forests of South America - Rogério R. Silva; Felipe Martello; Rodrigo Machado Feitosa; Otávio Guilherme M. Silva; Lívia Pires do Prado; Carlos Roberto F. Brandão; Emília Zoppas de Albuquerque; Maria Santina C. Morini; Jacques Hubert Charles Delabie; Erison Carlos dos Santos Monteiro; Agripino Emanuel Oliveira Alves; Alexander L. Wild; et al. (Ecology, 2022)
Ants, an ecologically successful and numerically dominant group of animals, play key ecological roles as soil engineers, predators, nutrient recyclers, and regulators of plant growth and reproduction in most terrestrial ecosystems. Further, ants are widely used as bioindicators of the ecological impact of land use. We gathered information of ant species in the Atlantic Forest of South America. The ATLANTIC ANTS data set, which is part of the ATLANTIC SERIES data papers, is a compilation of ant records from collections (18,713 records), unpublished data (29,651 records), and published sources (106,910 records; 1,059 references), including papers, theses, dissertations, and book chapters published from 1886 to 2020. In total, the data set contains 153,818 ant records from 7,636 study locations in the Atlantic Forest, representing 10 subfamilies, 99 genera, 1,114 ant species identified with updated taxonomic certainty, and 2,235 morphospecies codes. Our data set reflects the heterogeneity in ant records, which include ants sampled at the beginning of the taxonomic history of myrmecology (the 19th and 20th centuries) and more recent ant surveys designed to address specific questions in ecology and biology. The data set can be used by researchers to develop strategies to deal with different macroecological and region‐wide questions, focusing on assemblages, species occurrences, and distribution patterns. Furthermore, the data can be used to assess the consequences of changes in land use in the Atlantic Forest on different ecological processes. No copyright restrictions apply to the use of this data set, but we request that authors cite this data paper when using these data in publications or teaching events.

Benthic Cyanobacterial Diversity and Antagonistic Interactions in Abrolhos Bank: Allelopathy, Susceptibility to Herbivory, and Toxicity - Felipe de Vargas Ribeiro; Taiara Aguiar Caires; Marcela Alvarenga de Almeida Simões; Paulo Iiboshi Hargreaves; Livia Bonetti Villela; Giovana de Oliveira Fistarol; Alexandre Brauns Cazelgrandi; Guilherme Henrique Pereira-Filho; Rodrigo Leão de Moura; Renato Crespo Pereira; Paulo Sergio Salomon (Frontiers in Marine Science, 2022)
Benthic cyanobacterial mats (BCMs) are conspicuous components of coral reef communities, where they play key ecological roles as primary producers among others. BCMs often bloom and might outcompete neighboring benthic organisms, including reef-building corals. We investigated the cyanobacterial species composition of three BCMs morphotypes from the marginal reef complex of Abrolhos Bank (Southeastern Brazil). Also, we assessed their allelopathic effects on coral zooxanthellae, their susceptibility to herbivory by fish, and their toxicity to brine shrimp nauplii. Morphology and 16S rDNA sequencing unveiled the cyanobacteria Moorena bouillonii , Okeania erythroflocculosa , Adonisia turfae , Leptolyngbya sp., and Halomicronema sp. as components of BCMs from Abrolhos. BCMs cell-free filtrates and extracts exerted an allelopathic effect by reducing the growth of the ex hospite Symbiodinium sp. in culture. BCMs-only treatments remained untouched in field susceptibility assays in contrast to macroalgae only and mixed BCMs-macroalgae treatments that had the macroalgae fully removed by reef fish. Crude aqueous extracts from BCMs were toxic to brine shrimps in acute assays. Besides unveiling the diversity of BCMs consortia in Abrolhos, our results cast some light on their allelopathy, antiherbivory, and toxicity properties. These antagonistic interactions might promote adverse cascading effects during benthic cyanobacteria blooms and in gradual shifts to BCMs-dominated states.

Proximate Composition, Nutritional Lipid Quality, and Health Indices of Largemouth Bass ( Micropterus salmoides Lacépède, 1802) from Several Mediterranean Reservoirs - André Jorge; M. Graça Machado; Carlos M. Alexandre; Marco Gomes da Silva; Pedro R. Almeida; M. João Lança (Journal of Aquatic Food Product Technology, 2022)

Rumen fermentation and metabolic profile of rams fed with diets amended cottonseed cake - Fagton de Mattos Negrão; Anderson de Moura Zanine; Marinaldo Divino Ribeiro; Daniele de Jesus Ferreira; Alexandre Lima de Souza; Michelle de Oliveira Maia Parente; Henrique Nunes Parente; Rafael Henrique Pereira dos Reis; Túlio Otávio Jardim D.’Almeida Lins; Anny Graycy Vasconcelos de Oliveira Lima (Tropical Animal Health and Production, 2021)

Density and Abundance Estimation of Amazonian River Dolphins: Understanding Population Size Variability - Mariana Paschoalini; Fernando Trujillo; Miriam Marmontel; Federico Mosquera-Guerra; Renan Lopes Paitach; Heloise Pavanato Julião; Gabriel Melo Alves dos Santos; Paul André Van Damme; André Giovanni de Almeida Coelho; Mariana Escobar Wilson White; Alexandre Novaes Zerbini (Journal of Marine Science and Engineering, 2021)
The dolphins Inia geoffrensis—boto and Sotalia fluviatilis—tucuxi are threatened cetaceans inhabiting river ecosystems in South America; population numbers are still lacking for many areas. This paper provides density and abundance estimations of boto and tucuxi in 15 rivers sampled during the past nine years as part of a multinational research alliance. Visual boat-survey data collection protocols and analyses have been developed since 2012 (based on Distance Sampling methods) and recently reviewed (2019) to improve robustness and comparability. Differences across the sampled rivers and the analyzed river basins (Amazon and Orinoco) pointed to a density/population size gradient with lower densities and abundances observed in the Orinoco basin (0.9–1.5 ind./km²), passing through the eastern Amazon basin (2–5 ind./km²), and the largest numbers found at the central Brazilian Amazon (lower Purus River—2012 (14.5 boto/km², N = 7672; 17.1 tucuxi/km², N = 9238)). However, in other parts of the central Amazon, the density of dolphins was smaller than expected for high productive whitewater rivers (1–1.7 ind./km² in the Japurá and Solimões rivers). We attributed these differences to specific features of the basin (e.g., hydro-geomorphology) as well as to the cumulative effects of anthropogenic activities.

Effects of supplementation on production and age anticipation at first mating of ewe lambs in tropical pastures - Thais Fernanda Farias de Souza Arco; Camila Celeste Brandão Ferreira Ítavo; Luís Carlos Vinhas Ítavo; Maria Inês Lenz Souza; Alexandre Menezes Dias; Gelson dos Santos Difante; Eliane Vianna da Costa e Silva; Fernando de Almeida Borges; Dyego Gonçalves Lino Borges; Kedma Leonora da Silva Monteiro Ferelli; Bruna Junqueira Rodrigues; Aline Aparecida da Silva Miguel; et al. (Tropical Animal Health and Production, 2021)

Selection for papaya resistance to multiple diseases in a base population of recurrent selection - Ramon de Moraes; Marcelo Vivas; Derivaldo Pureza da Cruz; Renato Santa-Catarina; Rafael Nunes de Almeida; Yure Pequeno de Souza; Rogério Figueiredo Daher; Alexandre Pio Viana; Messias Gonzaga Pereira (Euphytica, 2021)

Bacterial cellulose biotextiles for the future of sustainable fashion: a review - Claudio José Galdino da Silva; Alexandre D’Lamare Maia de Medeiros; Julia Didier Pedrosa de Amorim; Helenise Almeida do Nascimento; Attilio Converti; Andrea Fernanda Santana Costa; Leonie Asfora Sarubbo (Environmental Chemistry Letters, 2021)

Water buffalo production in the Brazilian Amazon Basin: a review - Jamile Andréa Rodrigues da Silva; Alexandre Rossetto Garcia; André Martinho de Almeida; Andréia Santana Bezerra; José de Brito Lourenço Junior (Tropical Animal Health and Production, 2021)

First detailed insights into the life‐history traits of the alien shrimp Athanas nitescens (Decapoda: Alpheidae) in the western Atlantic - Régis A. Pescinelli; Fernando L. Mantelatto; Alexandre O. Almeida; Rogerio C. Costa (Marine Ecology, 2021)
Information on the population biology of alien species in non‐natural areas is essential to understanding their impacts on native species. Here, we investigated the life‐history traits, the propagule pressure and the supply potential of Athanas nitescens in a non‐native area. Sampling was monthly performed from April 2015 to March 2016 in an inter‐tidal estuary in the south‐eastern Brazilian coast. The population had a female‐biased sex ratio with a predominance of ovigerous females. Sexual dimorphism was evidenced by the mean body size and the positive allometry of chelipeds in males and of the second pleonal pleuron in females, evidencing an energy allocation to weaponry body structures and reproduction, respectively. The estimated size at which 50% of females reach functional sexual maturity was 3.3 mm of carapace length. The mean fecundity, 117 ± 40.03 eggs/female (53–263), had a positive correlation with the carapace length. The egg volume increased (83%) from the initial to the final stage of development. The presence of females carrying eggs in different stages of development indicates that A . nitescens is completing its life cycle in the studied region and shows a high propagule pressure. We provided the first insights into the biology of A . nitescens in Brazilian waters after the first record in 2009 in São Paulo coast, contributing to a better understanding of its biology and ecology in non‐natural areas.

Dynamics of marine predators off an oceanic island and implications for management of a preventative shark fishing program - Yuri Niella; Alexandre Wiefels; Ulian Almeida; Sébastien Jaquemet; Erwann Lagabrielle; Robert Harcourt; Victor Peddemors; David Guyomard (Marine Biology, 2021)

Agroecological practices to support tropical livestock farming systems: a Caribbean and Latin American perspective - Gisele Alexandre; Lylian Rodriguez; Javier Arece; José Delgadillo; Gary Wayne Garcia; Kurt Habermeier; André M. Almeida; Audrey Fanchone; Jean-Luc Gourdine; Harry Archimède (Tropical Animal Health and Production, 2021)

Fuel Consumption Between Two Soil Tillage Systems for Planting Sugarcane - Murilo Battistuzzi Martins; Fernanda Pacheco de Almeida Prado Bortolheiro; João Vitor Paulo Testa; Maria Márcia Pereira Sartori; Carlos Alexandre Costa Crusciol; Kléber Pereira Lanças (Sugar Tech, 2021)

NEOTROPICAL CARNIVORES: a data set on carnivore distribution in the Neotropics - Mariana Nagy‐Reis; Júlia Emi de Faria Oshima; Claudia Zukeran Kanda; Francesca Belem Lopes Palmeira; Fabiano Rodrigues de Melo; Ronaldo Gonçalves Morato; Lilian Bonjorne; Marcelo Magioli; Caroline Leuchtenberger; Fabio Rohe; Frederico Gemesio Lemos; Felipe Martello; et al. (Ecology, 2020)
Mammalian carnivores are considered a key group in maintaining ecological health and can indicate potential ecological integrity in landscapes where they occur. Carnivores also hold high conservation value and their habitat requirements can guide management and conservation plans. The order Carnivora has 84 species from 8 families in the Neotropical region: Canidae; Felidae; Mephitidae; Mustelidae; Otariidae; Phocidae; Procyonidae; and Ursidae. Herein, we include published and unpublished data on native terrestrial Neotropical carnivores (Canidae; Felidae; Mephitidae; Mustelidae; Procyonidae; and Ursidae). NEOTROPICAL CARNIVORES is a publicly available data set that includes 99,605 data entries from 35,511 unique georeferenced coordinates. Detection/non‐detection and quantitative data were obtained from 1818 to 2018 by researchers, governmental agencies, non‐governmental organizations, and private consultants. Data were collected using several methods including camera trapping, museum collections, roadkill, line transect, and opportunistic records. Literature (peer‐reviewed and grey literature) from Portuguese, Spanish and English were incorporated in this compilation. Most of the data set consists of detection data entries (n = 79,343; 79.7%) but also includes non‐detection data (n = 20,262; 20.3%). Of those, 43.3% also include count data (n = 43,151). The information available in NEOTROPICAL CARNIVORES will contribute to macroecological, ecological, and conservation questions in multiple spatio‐temporal perspectives. As carnivores play key roles in trophic interactions, a better understanding of their distribution and habitat requirements are essential to establish conservation management plans and safeguard the future ecological health of Neotropical ecosystems. Our data paper, combined with other large‐scale data sets, has great potential to clarify species distribution and related ecological processes within the Neotropics. There are no copyright restrictions and no restriction for using data from this data paper, as long as the data paper is cited as the source of the information used. We also request that users inform us of how they intend to use the data.

NEOTROPICAL ALIEN MAMMALS: a data set of occurrence and abundance of alien mammals in the Neotropics - Clarissa Alves da Rosa; Bruno R. Ribeiro; Vanesa Bejarano; Fernando Henrique Puertas; Adriana Bocchiglieri; Adriana Loeser dos Santos Barbosa; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adriele Aparecida Pereira; Adryelle Francisca de Souza Moreira; Agnis Cristiane de Souza; Aiesca Pellegrin; et al. (Ecology, 2020)
Biological invasion is one of the main threats to native biodiversity. For a species to become invasive, it must be voluntarily or involuntarily introduced by humans into a nonnative habitat. Mammals were among first taxa to be introduced worldwide for game, meat, and labor, yet the number of species introduced in the Neotropics remains unknown. In this data set, we make available occurrence and abundance data on mammal species that (1) transposed a geographical barrier and (2) were voluntarily or involuntarily introduced by humans into the Neotropics. Our data set is composed of 73,738 historical and current georeferenced records on alien mammal species of which around 96% correspond to occurrence data on 77 species belonging to eight orders and 26 families. Data cover 26 continental countries in the Neotropics, ranging from Mexico and its frontier regions (southern Florida and coastal‐central Florida in the southeast United States) to Argentina, Paraguay, Chile, and Uruguay, and the 13 countries of Caribbean islands. Our data set also includes neotropical species (e.g., Callithrix sp., Myocastor coypus , Nasua nasua) considered alien in particular areas of Neotropics. The most numerous species in terms of records are from Bos sp. ( n = 37,782), Sus scrofa ( n = 6,730), and Canis familiaris ( n = 10,084); 17 species were represented by only one record (e.g., S yncerus caffer, Cervus timorensis, Cervus unicolor, Canis latrans ). Primates have the highest number of species in the data set ( n = 20 species), partly because of uncertainties regarding taxonomic identification of the genera Callithrix, which includes the species Callithrix aurita, Callithrix flaviceps, Callithrix geoffroyi, Callithrix jacchus, Callithrix kuhlii, Callithrix penicillata , and their hybrids. This unique data set will be a valuable source of information on invasion risk assessments, biodiversity redistribution and conservation‐related research. There are no copyright restrictions. Please cite this data paper when using the data in publications. We also request that researchers and teachers inform us on how they are using the data.

Biodiversity of caridean shrimps on rocky bottoms of two preserved islands on the southeastern Brazilian coast - Isabela R. R. Moraes; Alexandre Oliveira Almeida; Valter José Cobo; Douglas Fernandes Rodrigues Alves; Thiago Maia Davanso; Antonio Leão Castilho (Marine Biology Research, 2020)

Algrizea Minor Sobral, Faria & Proença (Myrteae, Myrtaceae): chemical composition, antinociceptive, antimicrobial and antioxidant activity of essential oil - Bruno Oliveira de Veras; Yago Queiroz dos Santos; Fernanda Granja da Silva Oliveira; Jackson Roberto Guedes da Silva Almeida; Alexandre Gomes da Silva; Maria Tereza dos Santos Correia; Katharina Marques Diniz; João Ricardhis Saturnino de Oliveira; Vera Lúcia de Menezes Lima; Daniela Maria do Amaral Ferraz Navarro; Júlio César Ribeiro de Oliveira Farias de Aguiar; Maria Betânia Melo de Oliveira; et al. (Natural Product Research, 2020)

Characterization of planktonic and biofilm cells from two filamentous cyanobacteria using a shotgun proteomic approach - Maria João Leal Romeu; Dany Domínguez-Pérez; Daniela Almeida; João Morais; Alexandre Campos; Vítor Vasconcelos; Filipe J. M. Mergulhão (Biofouling, 2020)

Influence of land use on the performance of the WRF model in a humid tropical climate - Youssimar Georgynio Rosales Aylas; Wesley de Souza Campos Correa; Alexandre Magalhães Santiago; Neyval Costa Reis Junior; Taciana Toledo de Almeida Albuquerque; Jane Meri Santos; Davidson Martins Moreira (Theoretical and Applied Climatology, 2020)

Mesquite pod meal as an additive increases milk total solids, lactose, fat and protein content in dairy cows - Luzyanne Varjão Aguiar; Herymá Giovane de Oliveira Silva; Sergio Augusto de Albuquerque Fernandes; Dirlane Novais Caires; Abias Santos Silva; Alexandre Etzberger Feistauer; Henrique Almeida da Silva; Lázaro Costa da Silva; Soraia Vanessa Matarazzo; Márcio dos Santos Pedreira (Tropical Animal Health and Production, 2020)

Morphological Changes in Sugarcane Crop Induced by the Plant Growth-Promoting Bacterium Azospirillum brasilense - Ronaldo da Silva Viana; Bruno Rafael de Almeida Moreira; Lucas Aparecido Manzani Lisboa; Rômulo Sandu Junior; Thiago Assis Rodrigues Nogueira; Paulo Alexandre Monteiro de Figueiredo; Marcelo Carvalho Minhoto Teixeira Filho; Sergio Bispo Ramos (Sugar Tech, 2020)

Can Micronized Sulfur in Urea Reduce Ammoniacal Nitrogen Volatilization and Improve Maize Grain Yield? - Carlos Alexandre Costa Crusciol; Danilo Silva Almeida; Cleiton José Alves; Rogério Peres Soratto; Evelin Oliveira Krebsky; Eduardo Scarpari Spolidorio (Journal of Soil Science and Plant Nutrition, 2019)

Growth, Sexual Maturity and Dimorphism in Six Species of Snapping Shrimps of the Genus Alpheus (Decapoda: Alpheidae) - Ana Carla Costa-Souza; José Roberto Botelho de Souza; Alexandre Oliveira Almeida (Thalassas: An International Journal of Marine Sciences, 2019)

Effect of gluten diet on blood innate immune gene expressions and stool consistency in Spix’s Saddleback Tamarin (Leontocebus fuscicollis) raised in captivity - Taianara Tocantins Gomes Almeida; Maria Vivina Barros Monteiro; Rafaelle Casseb Guimarães; Alexandre Rosário Casseb; Michael Alan Huffman; Evonnildo Costa Gonçalves; Frederico Ozanan Barros Monteiro; Ednaldo Silva Filho (Molecular Biology Reports, 2019)

NEOTROPICAL XENARTHRANS: a data set of occurrence of xenarthran species in the Neotropics - Paloma Marques Santos; Adriana Bocchiglieri; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adryelle Moreira; Agnis Cristiane de Souza; Agustin Manuel Abba; Agustin Paviolo; Ailin Gatica; Akyllan Zoppi Medeiro; Alan Nilo Costa; Alberto Gonzalez Gallina; et al. (Ecology, 2019)
Xenarthrans—anteaters, sloths, and armadillos—have essential functions for ecosystem maintenance, such as insect control and nutrient cycling, playing key roles as ecosystem engineers. Because of habitat loss and fragmentation, hunting pressure, and conflicts with domestic dogs, these species have been threatened locally, regionally, or even across their full distribution ranges. The Neotropics harbor 21 species of armadillos, 10 anteaters, and 6 sloths. Our data set includes the families Chlamyphoridae (13), Dasypodidae (7), Myrmecophagidae (3), Bradypodidae (4), and Megalonychidae (2). We have no occurrence data on Dasypus pilosus (Dasypodidae). Regarding Cyclopedidae, until recently, only one species was recognized, but new genetic studies have revealed that the group is represented by seven species. In this data paper, we compiled a total of 42,528 records of 31 species, represented by occurrence and quantitative data, totaling 24,847 unique georeferenced records. The geographic range is from the southern United States, Mexico, and Caribbean countries at the northern portion of the Neotropics, to the austral distribution in Argentina, Paraguay, Chile, and Uruguay. Regarding anteaters, Myrmecophaga tridactyla has the most records ( n = 5,941), and Cyclopes sp. have the fewest ( n = 240). The armadillo species with the most data is Dasypus novemcinctus ( n = 11,588), and the fewest data are recorded for Calyptophractus retusus ( n = 33). With regard to sloth species, Bradypus variegatus has the most records ( n = 962), and Bradypus pygmaeus has the fewest ( n = 12). Our main objective with Neotropical Xenarthrans is to make occurrence and quantitative data available to facilitate more ecological research, particularly if we integrate the xenarthran data with other data sets of Neotropical Series that will become available very soon (i.e., Neotropical Carnivores, Neotropical Invasive Mammals, and Neotropical Hunters and Dogs). Therefore, studies on trophic cascades, hunting pressure, habitat loss, fragmentation effects, species invasion, and climate change effects will be possible with the Neotropical Xenarthrans data set. Please cite this data paper when using its data in publications. We also request that researchers and teachers inform us of how they are using these data.

Interaction with Pantoea agglomerans Modulates Growth and Melanization of Sporothrix brasiliensis and Sporothrix schenckii - Rodrigo Almeida-Paes; Fábio Brito-Santos; Manoel Marques Evangelista Oliveira; Alexandre Melo Bailão; Clayton Luiz Borges; Glauber Ribeiro de Souza Araújo; Susana Frases; Célia Maria de Almeida Soares; Rosely Maria Zancopé-Oliveira (Mycopathologia, 2019)

Optimization of treating phenol from wastewater through the TiO2-catalyzed advanced oxidation process and response surface methodology - Camila Oliveira Guimarães; Alexandre Boscaro França; Gisella Rossana Lamas Samanamud; Eduardo Prado Baston; Renata Carolina Zanetti Lofrano; Carla Cristina Almeida Loures; Luzia Lima Rezende Naves; Fabiano Luiz Naves (Environmental Monitoring and Assessment, 2019)

ATLANTIC BIRD TRAITS : a data set of bird morphological traits from the Atlantic forests of South America - Rodolpho Credo Rodrigues; Érica Hasui; Julia Camara Assis; João Carlos Castro Pena; Renata L. Muylaert; Vinicius Rodrigues Tonetti; Felipe Martello; André Luis Regolin; Thiago Vernaschi Vieira da Costa; Mauro Pichorim; Eduardo Carrano; Leonardo Esteves Lopes; et al. (Ecology, 2019)
Scientists have long been trying to understand why the Neotropical region holds the highest diversity of birds on Earth. Recently, there has been increased interest in morphological variation between and within species, and in how climate, topography, and anthropogenic pressures may explain and affect phenotypic variation. Because morphological data are not always available for many species at the local or regional scale, we are limited in our understanding of intra‐ and interspecies spatial morphological variation. Here, we present the ATLANTIC BIRD TRAITS , a data set that includes measurements of up to 44 morphological traits in 67,197 bird records from 2,790 populations distributed throughout the Atlantic forests of South America. This data set comprises information, compiled over two centuries (1820–2018), for 711 bird species, which represent 80% of all known bird diversity in the Atlantic Forest. Among the most commonly reported traits are sex ( n = 65,717), age ( n = 63,852), body mass ( n = 58,768), flight molt presence ( n = 44,941), molt presence ( n = 44,847), body molt presence ( n = 44,606), tail length ( n = 43,005), reproductive stage ( n = 42,588), bill length ( n = 37,409), body length ( n = 28,394), right wing length ( n = 21,950), tarsus length ( n = 20,342), and wing length ( n = 18,071). The most frequently recorded species are Chiroxiphia caudata ( n = 1,837), Turdus albicollis ( n = 1,658), Trichothraupis melanops ( n = 1,468), Turdus leucomelas ( n = 1,436), and Basileuterus culicivorus ( n = 1,384). The species recorded in the greatest number of sampling localities are Basileuterus culicivorus ( n = 243), Trichothraupis melanops ( n = 242), Chiroxiphia caudata ( n = 210), Platyrinchus mystaceus ( n = 208), and Turdus rufiventris ( n = 191). ATLANTIC BIRD TRAITS ( ABT ) is the most comprehensive data set on measurements of bird morphological traits found in a biodiversity hotspot; it provides data for basic and applied research at multiple scales, from individual to community, and from the local to the macroecological perspectives. No copyright or proprietary restrictions are associated with the use of this data set. Please cite this data paper when the data are used in publications or teaching and educational activities.

ATLANTIC EPIPHYTES : a data set of vascular and non‐vascular epiphyte plants and lichens from the Atlantic Forest - Flavio Nunes Ramos; Sara Ribeiro Mortara; Nathalia Monalisa‐Francisco; João Pedro Costa Elias; Luiz Menini Neto; Leandro Freitas; Rodrigo Kersten; André Márcio Amorim; Fernando Bittencourt Matos; André Felippe Nunes‐Freitas; Suzana Alcantara; Marcia Helena Nagahama Alexandre; et al. (Ecology, 2019)
Epiphytes are hyper‐diverse and one of the frequently undervalued life forms in plant surveys and biodiversity inventories. Epiphytes of the Atlantic Forest, one of the most endangered ecosystems in the world, have high endemism and radiated recently in the Pliocene. We aimed to (1) compile an extensive Atlantic Forest data set on vascular, non‐vascular plants (including hemiepiphytes), and lichen epiphyte species occurrence and abundance; (2) describe the epiphyte distribution in the Atlantic Forest, in order to indicate future sampling efforts. Our work presents the first epiphyte data set with information on abundance and occurrence of epiphyte phorophyte species. All data compiled here come from three main sources provided by the authors: published sources (comprising peer‐reviewed articles, books, and theses), unpublished data, and herbarium data. We compiled a data set composed of 2,095 species, from 89,270 holo/hemiepiphyte records, in the Atlantic Forest of Brazil, Argentina, Paraguay, and Uruguay, recorded from 1824 to early 2018. Most of the records were from qualitative data (occurrence only, 88%), well distributed throughout the Atlantic Forest. For quantitative records, the most common sampling method was individual trees (71%), followed by plot sampling (19%), and transect sampling (10%). Angiosperms (81%) were the most frequently registered group, and Bromeliaceae and Orchidaceae were the families with the greatest number of records (27,272 and 21,945, respectively). Ferns and Lycophytes presented fewer records than Angiosperms, and Polypodiaceae were the most recorded family, and more concentrated in the Southern and Southeastern regions. Data on non‐vascular plants and lichens were scarce, with a few disjunct records concentrated in the Northeastern region of the Atlantic Forest. For all non‐vascular plant records, Lejeuneaceae, a family of liverworts, was the most recorded family. We hope that our effort to organize scattered epiphyte data help advance the knowledge of epiphyte ecology, as well as our understanding of macroecological and biogeographical patterns in the Atlantic Forest. No copyright restrictions are associated with the data set. Please cite this Ecology Data Paper if the data are used in publication and teaching events.

REM sleep behavior disorder in patients with Parkinson’s disease: clinical and polysomnographic characteristics - Manoel Alves Sobreira-Neto; Márcio Alexandre Pena-Pereira; Emmanuelle Silva Tavares Sobreira; Marcos Hortes Nisihara Chagas; Carlos Maurício Oliveira de Almeida; Regina Maria França Fernandes; Vitor Tumas; Alan Luiz Eckeli (Sleep and Biological Rhythms, 2019)

Shotgun proteomics of ascidians tunic shed light into the interaction between host and their associated bacteria - Ana Matos; Dany Domínguez-Pérez; Daniela Almeida; Alexandre Campos; Hugo Osório; Vitor Vasconcelos; Agostinho Antunes (Frontiers in Marine Science, 2019)

ATLANTIC ‐ PRIMATES : a dataset of communities and occurrences of primates in the Atlantic Forests of South America - Laurence Culot; Lucas Augusto Pereira; Ilaria Agostini; Marco Antônio Barreto de Almeida; Rafael Souza Cruz Alves; Izar Aximoff; Alex Bager; María Celia Baldovino; Thiago Ribas Bella; Júlio César Bicca‐Marques; Caryne Braga; Carlos Rodrigo Brocardo; et al. (Ecology, 2019)
Primates play an important role in ecosystem functioning and offer critical insights into human evolution, biology, behavior, and emerging infectious diseases. There are 26 primate species in the Atlantic Forests of South America, 19 of them endemic. We compiled a dataset of 5,472 georeferenced locations of 26 native and 1 introduced primate species, as hybrids in the genera Callithrix and Alouatta . The dataset includes 700 primate communities, 8,121 single species occurrences and 714 estimates of primate population sizes, covering most natural forest types of the tropical and subtropical Atlantic Forest of Brazil, Paraguay and Argentina and some other biomes. On average, primate communities of the Atlantic Forest harbor 2 ± 1 species (range = 1–6). However, about 40% of primate communities contain only one species. Alouatta guariba (N = 2,188 records) and Sapajus nigritus (N = 1,127) were the species with the most records. Callicebus barbarabrownae (N = 35), Leontopithecus caissara (N = 38), and Sapajus libidinosus (N = 41) were the species with the least records. Recorded primate densities varied from 0.004 individuals/km 2 ( Alouatta guariba at Fragmento do Bugre, Paraná, Brazil) to 400 individuals/km 2 ( Alouatta caraya in Santiago, Rio Grande do Sul, Brazil). Our dataset reflects disparity between the numerous primate census conducted in the Atlantic Forest, in contrast to the scarcity of estimates of population sizes and densities. With these data, researchers can develop different macroecological and regional level studies, focusing on communities, populations, species co‐occurrence and distribution patterns. Moreover, the data can also be used to assess the consequences of fragmentation, defaunation, and disease outbreaks on different ecological processes, such as trophic cascades, species invasion or extinction, and community dynamics. There are no copyright restrictions. Please cite this Data Paper when the data are used in publications. We also request that researchers and teachers inform us of how they are using the data.

Antioxidant and antidepressant-like effects of Eugenia catharinensis D. Legrand in an animal model of depression induced by corticosterone - Sara Cristiane Barauna; Débora Delwing-Dal Magro; Maitê Beatriz Brueckheimer; Thayná P. Maia; Geraldo Antonio Bunick Neto Sala; André Wolff Döhler; Mateus Campestrini Harger; Dayse Fabiane Machado de Melo; André Luís de Gasper; Michele Debiasi Alberton; Diogo Alexandre Siebert; Gustavo Amadeu Micke; et al. (Metabolic Brain Disease, 2018)

Evaluation of the effectiveness of red mud-supported catalysts in combination with ozone and TiO2 in the treatment of solution containing benzene, toluene, and xylene - Bernardo Alves de Lima; Pedro Paulo Rocha de Castro; Alexandre Boscaro França; Eduardo Prado Baston; Renata Carolina Zanetti Lofrano; Gisella Rossana Lamas Samanamud; Carla Cristina Almeida Loures; Luzia Lima Rezende Naves; Fabiano Luiz Naves (Environmental Monitoring and Assessment, 2018)

Characterisation of phenolic compounds of the ethyl acetate fraction from Tabernaemontana catharinensis and its potential antidepressant-like effect - Nathielli Nayara Pauleti; Jonas Mello; Diogo Alexandre Siebert; Gustavo Amadeu Micke; Cláudia Almeida Coelho de Albuquerque; Michele Debiasi Alberton; Sara Cristiane Barauna (Natural Product Research, 2018)

Population structure, relative growth and morphological sexual maturity of the snapping shrimp Alpheus brasileiro Anker, 2012 (Caridea: Alpheidae) from the south-eastern coast of Brazil - Régis Augusto Pescinelli; Alexandre Oliveira Almeida; Rogério Caetano Costa (Marine Biology Research, 2018)

Multiple source spatial cluster detection via multi-criteria analysis - Alexandre C. L. Almeida; Luiz H. Duczmal; André L. F. Cançado; Fabio R. da Silva (Environmental and Ecological Statistics, 2018)

Deltamethrin-induced nuclear erythrocyte alteration and damage to the gills and liver of Colossoma macropomum - Fernanda dos Santos Cunha; Natalino da Costa Sousa; Rudã Fernandes Brandão Santos; Juliana Oliveira Meneses; Márcia Valéria Silva do Couto; Fabrício Tavares Cunha de Almeida; José Guedes de Sena Filho; Paulo César Falanghe Carneiro; Alexandre Nizio Maria; Rodrigo Yudi Fujimoto (Environmental Science and Pollution Research, 2018)

Population Structure of the Shrimp Alpheus estuariensis (Caridea: Alpheidae) in a Tropical Estuarine Tidal Mudflat - Ana Carla Costa-Souza; José Roberto Botelho de Souza; Marina de Sá Leitão Câmara de Araújo; Alexandre Oliveira Almeida (Thalassas: An International Journal of Marine Sciences, 2018)

BacHBerry: BACterial Hosts for production of Bioactive phenolics from bERRY fruits - Alexey Dudnik; A. Filipa Almeida; Ricardo Andrade; Barbara Avila; Pilar Bañados; Diane Barbay; Jean-Etienne Bassard; Mounir Benkoulouche; Michael Bott; Adelaide Braga; Dario Breitel; Rex Brennan; et al. (Phytochemistry Reviews, 2018)

Normal boundary intersection applied as multivariate and multiobjective optimization in the treatment of amoxicillin synthetic solution - Deberton Moura; Vithor Barcelos; Gisella Rossana Lamas Samanamud; Alexandre Boscaro França; Renata Lofrano; Carla Cristina Almeida Loures; Luzia Lima Rezende Naves; Mateus Souza Amaral; Fabiano Luiz Naves (Environmental Monitoring and Assessment, 2018)

Variation in the composition and activity of ants on defense of host plant Turnera subulata (Turneraceae): strong response to simulated herbivore attacks and to herbivore’s baits - Nayara G. Cruz; Paulo F. Cristaldo; Leandro Bacci; Camilla S. Almeida; Gabriela P. Camacho; Alisson S. Santana; Efrem J. M. Ribeiro; Alexandre P. Oliveira; Abraão A. Santos; Ana P. A. Araújo (Arthropod-Plant Interactions, 2018)

Effects of fibre digestibility and level of roughage on performance and rumen fermentation of finishing beef cattle - Dannylo Oliveira Sousa; Bruno de Sousa Mesquita; Alexandre Vaz Pires; Miguel Henrique de Almeida Santana; Luis Felipe Prada Silva (Tropical Animal Health and Production, 2017)

Embryo Production of Two Sympatric Snapping Shrimps of the Genus Alpheus (Caridea: Alpheidae) from Northeastern Brazil: a Comparative Approach - Guidomar Oliveira Soledade; Patricia Souza Santos; Régis Augusto Pescinelli; Rogério Caetano Costa; Alexandre Oliveira Almeida (Thalassas: An International Journal of Marine Sciences, 2017)

Chemical composition of fine particles (PM2.5): water-soluble organic fraction and trace metals - Luciana Maria Baptista Ventura; Vinícius Lionel Mateus; Alexandre Collett Solberg Leitão de Almeida; Kristine Bruce Wanderley; Fabio Tadashi Taira; Tatiana D. Saint’Pierre; Adriana Gioda (Air Quality, Atmosphere & Health, 2017)

Inheritance of resistance to Meloidogyne enterolobii and individual selection in segregating populations of Psidium spp - Vicente Martins Gomes; Rodrigo Moreira Ribeiro; Alexandre Pio Viana; Ricardo Moreira de Souza; Eileen Azevedo Santos; Daniele Lima Rodrigues; Odimar Ferreira de Almeida (European Journal of Plant Pathology, 2017)

Copper/Zinc Bioaccumulation and the Effect of Phytotoxicity on the Growth of Lettuce (Lactuca sativa L.) in Non-contaminated, Metal-Contaminated and Swine Manure-Enriched Soils - Mariane Wolf; Dilmar Baretta; Valter A. Becegato; Vitor de C. Almeida; Alexandre T. Paulino (Water, Air, & Soil Pollution, 2017)

Response of Application of Growth Inhibitors on Sugarcane Productivity and Sucrose Accumulation in the Middle of Cropping Season in Brazil - Carlos Alexandre Costa Crusciol; Glauber Henrique Pereira Leite; Gabriela Ferraz de Siqueira; Marcelo de Almeida Silva (Sugar Tech, 2017)

Restoration of areas degraded by alluvial sand mining: use of soil microbiological activity and plant biomass growth to assess evolution of restored riparian vegetation - Graziela R. Venson; Rosemeri C. Marenzi; Tito César M. Almeida; Alexandre Deschamps-Schmidt; Renan C. Testolin; Leonardo R. Rörig; Claudemir M. Radetski (Environmental Monitoring and Assessment, 2017)

Effects of dietary Gracilaria sp. and Alaria sp. supplementation on growth performance, metabolic rates and health in meagre (Argyrosomus regius) subjected to pathogen infection - Maria João Peixoto; Emílio Salas-Leitón; Francisca Brito; Luís Ferreira Pereira; Jon C. Svendsen; Teresa Baptista; Rui Pereira; Helena Abreu; Pedro Alexandre Reis; José Fernando Magalhães Gonçalves; Rodrigo Otávio de Almeida Ozório (Journal of Applied Phycology, 2017)

Sociopolitical and economic elements to explain the environmental performance of countries - Thiago Alexandre das Neves Almeida; Isabel-María García-Sánchez (Environmental Science and Pollution Research, 2017)

Effects of Chrysosporum (Aphanizomenon) ovalisporum extracts containing cylindrospermopsin on growth, photosynthetic capacity, and mineral content of carrots (Daucus carota) - Remedios Guzmán-Guillén; Alexandre Campos; Joana Machado; Marisa Freitas; Joana Azevedo; Edgar Pinto; Agostinho Almeida; Ana M. Cameán; Vitor Vasconcelos (Ecotoxicology, 2017)

Persistence of a dominant bovine lineage of group B S treptococcus reveals genomic signatures of host adaptation - Alexandre Almeida; Cinthia Alves‐Barroco; Elisabeth Sauvage; Ricardo Bexiga; Pedro Albuquerque; Fernando Tavares; Ilda Santos‐Sanches; Philippe Glaser (Environmental Microbiology, 2016)
Summary Group B Streptococcus (GBS) is a host‐generalist species, most notably causing disease in humans and cattle. However, the differential adaptation of GBS to its two main hosts, and the risk of animal to human infection remain poorly understood. Despite improvements in control measures across Europe, GBS is still one of the main causative agents of bovine mastitis in Portugal. Here, by whole‐genome analysis of 150 bovine GBS isolates we discovered that a single CC61 clone is spreading throughout Portuguese herds since at least the early 1990s, having virtually replaced the previous GBS population. Mutations within an iron/manganese transporter were independently acquired by all of the CC61 isolates, underlining a key adaptive strategy to persist in the bovine host. Lateral transfer of bacteriocin production and antibiotic resistance genes also underscored the contribution of the microbial ecology and genetic pool within the bovine udder environment to the success of this clone. Compared to strains of human origin, GBS evolves twice as fast in bovines and undergoes recurrent pseudogenizations of human‐adapted traits. Our work provides new insights into the potentially irreversible adaptation of GBS to the bovine environment.

Connectivity maintain mammal assemblages functional diversity within agricultural and fragmented landscapes - Marcelo Magioli; Katia Maria Paschoaletto Micchi de Ferraz; Eleonore Zulnara Freire Setz; Alexandre Reis Percequillo; Michelle Viviane de Sá Santos Rondon; Vanessa Villanova Kuhnen; Mariana Cristina da Silva Canhoto; Karen Evelyn Almeida dos Santos; Claudia Zukeran Kanda; Gabriela de Lima Fregonezi; Helena Alves do Prado; Mitra Katherina Ferreira; et al. (European Journal of Wildlife Research, 2016)

Resource availability influences aggression and response to chemical cues in the Neotropical termite Nasutitermes aff. coxipoensis (Termitidae: Nasutitermitinae) - Paulo F. Cristaldo; Ana P. A. Araújo; Camilla S. Almeida; Nayara G. Cruz; Efrem J. M. Ribeiro; Marcos L. C. Rocha; Alisson S. Santana; Abraão A. Santos; Alexandre Passos; Og De Souza; Daniela F. Florencio (Behavioral Ecology and Sociobiology, 2016)

Extraction process optimization of sulfated galactan-rich fractions from Hypnea musciformis in order to obtain antioxidant, anticoagulant, or immunomodulatory polysaccharides - Monique Gabriela das Chagas Faustino Alves; Jailma Almeida-Lima; Almino Afonso Oliveria Paiva; Edda Lisboa Leite; Hugo Alexandre Oliveira Rocha (Journal of Applied Phycology, 2016)

Effect of different diets on growth and survival of the White-Spotted Jellyfish, Phyllorhiza punctata - Miranda Fábio Alexandre; Chambel João; Almeida Catarina; Pires Damiana; Duarte Inês; Esteves Liliana; Maranhão Paulo (Frontiers in Marine Science, 2016)

Horizontal study of vaccinia virus infections in an endemic area: epidemiologic, phylogenetic and economic aspects - Felipe L. Assis; Ana Paula M. Franco-Luiz; Luis M. Paim; Graziele P. Oliveira; Alexandre F. Pereira; Gabriel M. F. de Almeida; Leandra B. Figueiredo; Adriano Tanus; Giliane S. Trindade; Paulo P. Ferreira; Erna G. Kroon; Jônatas S. Abrahão (Archives of Virology, 2015)

Inheritance study and linkage mapping of resistance loci to Hemileia vastatrix in Híbrido de Timor UFV 443-03 - Kátia Nogueira Pestana; Alexandre Sandri Capucho; Eveline Teixeira Caixeta; Dênia Pires de Almeida; Eunize Maciel Zambolim; Cosme Damião Cruz; Laércio Zambolim; Antônio Alves Pereira; Antonio Carlos Baião de Oliveira; Ney Sussumu Sakiyama (Tree Genetics & Genomes, 2015)

Evaluation of thermal comfort, physiological, hematological, and seminal features of buffalo bulls in an artificial insemination station in a tropical environment - Daniel Vale Barros; Lilian Kátia Ximenes Silva; José de Brito Lourenço; Aluizio Otávio Almeida da Silva; André Guimarães Maciel e Silva; Irving Montanar Franco; Carlos Magno Chaves Oliveira; Patrícia Tholon; Lucieta Guerreiro Martorano; Alexandre Rossetto Garcia (Tropical Animal Health and Production, 2015)

Tadpole richness in riparian areas is determined by niche-based and neutral processes - Alexandre Pinheiro de Almeida; Domingos de Jesus Rodrigues; Michel Varajão Garey; Marcelo Menin (Hydrobiologia, 2015)

Starch levels on performance, milk composition and energy balance of lactating dairy cows - Carolina Almeida Carmo; Fernanda Batistel; Jonas de Souza; Junio Cesar Martinez; Paulo Correa; Alexandre Mendonça Pedroso; Flávio Augusto Portela Santos (Tropical Animal Health and Production, 2015)

Evaluating a vertical slot fishway in the recolonization of upstream stretch of River Mondego that was not available to sea lamprey - Pereira Esmeralda; Quintella Bernardo; Mateus Catarina; Alexandre Carlos; Cardoso Gabriela; Belo Ana; Telhado Ana; Quadrado Maria; De Almeida Pedro (Frontiers in Marine Science, 2015)

Monitoring anadromous fish populations in a context of habitat fragmentation and commercial exploitation - Cardoso Gabriela; Quintella Bernardo; Mateus Catarina; Alexandre Carlos; Belo Ana; Pereira Esmeralda; Telhado Ana; Quadrado Maria; De Almeida Pedro (Frontiers in Marine Science, 2015)

Effects of flow regulation in the life-cycles of a Mediterranean cyprinid species, the Iberian chub (Squalius carolitertii Doadrio, 1988) - Alexandre Carlos; Ferreira Teresa; De Almeida Pedro (Frontiers in Marine Science, 2015)

Androgen receptor-mediated regulation of adrenocortical activity in the sand rat, Psammomys obesus - Abdelouafi Benmouloud; Zaina Amirat; Farida Khammar; Alexandre V. Patchev; Jean M. Exbrayat; Osborne F. X. Almeida (Journal of Comparative Physiology B, 2014)

The effect of sex and genotype on growth performance, feed efficiency, and carcass traits of local sheep group Pantaneiro and Texel or Santa Inês crossbred finished on feedlot - Fernando Miranda de Vargas Junior; Charles Ferreira Martins; Guilherme dos Santos Pinto; Marcos Barbosa Ferreira; Hélio de Almeida Ricardo; André Gustavo Leão; Alexandre Rodrigo Mendes Fernandes; Alfredo Teixeira (Tropical Animal Health and Production, 2014)

Interaction of Curcumin with Manganese May Compromise Metal and Neurotransmitter Homeostasis in the Hippocampus of Young Mice - Ariana Ern Schmitz; Paulo Alexandre de Oliveira; Luiz F. de Souza; Danilo Grünig Humberto da Silva; Samara Danielski; Danúbia Bonfanti Santos; Eduardo Alves de Almeida; Rui Daniel Prediger; Andrew Fisher; Marcelo Farina; Alcir Luiz Dafre (Biological Trace Element Research, 2014)

Gold complexes with benzimidazole derivatives: synthesis, characterization and biological studies - Vinicius Zamprogno Mota; Gustavo Senra Gonçalves de Carvalho; Adilson David da Silva; Luiz Antônio Sodré Costa; Patrícia de Almeida Machado; Elaine Soares Coimbra; Carmen Veríssima Ferreira; Silvia Mika Shishido; Alexandre Cuin (BioMetals, 2014)

Guava decline: effect of root exudates from Meloidogyne enterolobii-parasitized plants on Fusarium solani in vitro and on growth and development of guava seedlings under controlled conditions - Vicente Martins Gomes; Ricardo Moreira Souza; Silvaldo Felipe da Silveira; Alexandre Macedo Almeida (European Journal of Plant Pathology, 2013)

Cytotoxic and leishmanicidal properties of garcinielliptone FC, a prenylated benzophenone from Platonia insignis - Joaquim S. Costa Júnior; Antonia Amanda Cardoso de Almeida; Alexandre de Barros Falcão Ferraz; Raíssa Rebés Rossatto; Teresinha G. Silva; Paulo B.N. Silva; Gardenia C.G. Militão; Antonia Maria das Graças Lopes Citó; Lorena Citó Lopes Resende Santana; Fernando Aécio de Amorim Carvalho; Rivelilson M. Freitas (Natural Product Research, 2013)

Isolation of microsatellite loci in the Amazon sailfin catfish Pterygoplichlhys pardalis (Castelneau, 1855) (Teleostei: Loricariidae) - Rosalina P. Pereira; Carlos Henrique dos A. dos Santos; Priscila Roberta M. Nascimento; Gisele T. Clímaco; Adna Cristina B. Sousa; Tatiana Campos; Alexandre Manoel K. Vergueiro-Júnior; Maria N. Paula-Silva; Vera Maria F. Almeida-Val (Conservation Genetics Resources, 2012)

An antimicrobial diketopiperazine alkaloid and co-metabolites from an endophytic strain of Gliocladium isolated from Strychnos cf. toxifera - Hector Henrique Ferreira Koolen; Elzalina Ribeiro Soares; Felipe Moura Araújo da Silva; Antonia Queiroz Lima de Souza; Lívia Soman de Medeiros; Edson Rodrigues Filho; Richardson Alves de Almeida; Ismael Alexandre Ribeiro; Cláudia do Ó Pessoa; Manoel Odorico de Morais; Patrícia Marçal da Costa; Afonso Duarte Leão de Souza (Natural Product Research, 2012)

Evaluating the possible anticoagulant and antioxidant effects of sulfated polysaccharides from the tropical green alga Caulerpa cupressoides var. flabellata - Mariana Santana Santos Pereira Costa; Leandro Silva Costa; Sara Lima Cordeiro; Jailma Almeida-Lima; Nednaldo Dantas-Santos; Kaline Dantas Magalhães; Diego Araujo Sabry; Ivan Rui Lopes Albuquerque; Marcia Rodrigues Pereira; Edda Lisboa Leite; Hugo Alexandre Oliveira Rocha (Journal of Applied Phycology, 2012)

Confirmation and characterization of interspecific hybrids of Passiflora L. (Passifloraceae) for ornamental use - Eileen Azevedo Santos; Margarete Magalhães Souza; Priscilla Patrocínio Abreu; Leo Duc Haa Carson Schwartzhaupt da Conceição; Ioná Santos Araújo; Alexandre Pio Viana; Alex-Alan Furtado de Almeida; Jôsie Cloviane de Oliveira Freitas (Euphytica, 2012)

Increased basal plasma brain-derived neurotrophic factor levels in sprint runners - Paulo Roberto Correia; Fulvio Alexandre Scorza; Sérgio Gomes da Silva; Aline Pansani; Michelle Toscano-Silva; Antonio Carlos de Almeida; Ricardo Mario Arida (Neuroscience Bulletin, 2011)

Two novel Ty1-copia retrotransposons isolated from coffee trees can effectively reveal evolutionary relationships in the Coffea genus (Rubiaceae) - Perla Hamon; Pierre-Olivier Duroy; Christine Dubreuil-Tranchant; Paulo Mafra D’Almeida Costa; Caroline Duret; Norosoa J. Razafinarivo; Emmanuel Couturon; Serge Hamon; Alexandre de Kochko; Valérie Poncet; Romain Guyot (Molecular Genetics and Genomics, 2011)

Genes Potentially Relevant in the Parasitic Phase of the Fungal Pathogen Paracoccidioides brasiliensis - Clayton Luiz Borges; Alexandre Melo Bailão; Sonia N. Báo; Maristela Pereira; Juliana Alves Parente; Célia Maria de Almeida Soares (Mycopathologia, 2011)

Tunicamycin inhibition of N-glycosylation of α-glucosidase from Aspergillus niveus: partial influence on biochemical properties - Tony Márcio Silva; Fausto Bruno Dos Reis Almeida; André Ricardo de Lima Damásio; Alexandre Maller; Michele Michelin; João Atílio Jorge; Ebert Seixas Hanna; Maria Cristina Roque-Barreira; Héctor F. Terenzi; Maria de Lourdes Teixeira de Moraes Poliz (Biotechnology Letters, 2010)

A device to improve the Schleger and Turner method for sweating rate measurements - Alfredo Manuel Franco Pereira; Alexandre Alves; Paulo Infante; Evaldo A. L. Titto; Flávio Baccari; J. A. Afonso Almeida (International Journal of Biometeorology, 2010)

Purification and biochemical characterization of a novel α-glucosidase from Aspergillus niveus - Tony Marcio da Silva; Michele Michelin; Andre Ricardo de Lima Damásio; Alexandre Maller; Fausto Bruno Dos Reis Almeida; Roberto Ruller; Richard John Ward; José Cesar Rosa; João Atilio Jorge; Héctor Francisco Terenzi; Maria de Lourdes Teixeira de Moraes Poliz (Antonie van Leeuwenhoek, 2009)

High frequency of BF mosaic genomes among HIV-1-infected children from Sao Paulo, Brazil - Cristina Mendes de Oliveira; Flávia Jacqueline Almeida; Rosangela Rodrigues; Marcia Crozatti; Carla Maria Pasquareli Vazquez; Maria do Socorro Carneiro Ferrão; Alexandre Ely Campeas; Silvia Regina Marques; Eitan Naaman Berezin; Luis Fernando de Macedo Brígido (Archives of Virology, 2008)

Comparison of transcription of multiple genes during mycelia transition to yeast cells of Paracoccidioides brasiliensis reveals insights to fungal differentiation and pathogenesis - Juliana Alves Parente; Clayton Luiz Borges; Alexandre Melo Bailão; Maria Sueli S. Felipe; Maristela Pereira; Célia Maria de Almeida Soares (Mycopathologia, 2008)

Purification and in vitro refolding of maize chloroplast transglutaminase over-expressed in Escherichia coli - Patricia K. Carvajal-Vallejos; Alexandre Campos; Pablo Fuentes-Prior; Enrique Villalobos; André M. Almeida; Eduard Barberà; José María Torné; Mireya Santos (Biotechnology Letters, 2007)

Tumor necrosis factor-α promoter polymorphism TNF2 is associated with a stronger delayed-type hypersensivity reaction in the skin of borderline tuberculoid leprosy patients - Milton O. Moraes; Nádia C. Duppre; Philip N. Suffys; Adalberto R. Santos; Alexandre S. Almeida; José A. C. Nery; Elizabeth P. Sampaio; Euzenir N. Sarno (Immunogenetics, 2001)